Solid electrolyte, method of preparing same, and secondary battery including same
By developing a solid electrolyte containing metal oxides, the problems of electrolyte leakage and thermal runaway in lithium-ion batteries are solved, and the battery performance and energy density are improved.
Patent Information
- Application Number
- CN202411405242.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-07
- Filing Date
- 2024-10-10
- Publication Date
- 2025-04-11
AI Technical Summary
Existing lithium-ion batteries have the risk of electrolyte leakage and thermal runaway, and liquid electrolytes are prone to cause electronic equipment failure.
A solid electrolyte is developed, using metal oxides as the main components, including lithium, silicon, boron and metals such as iron, chromium, lanthanum or thallium, with glass structure and excellent electrochemical stability and ionic conductivity, and is prepared by specific heat treatment methods.
The solid electrolyte has improved deformability and low temperature formability, reducing the risk of leakage and thermal runaway in the battery, while improving the performance and energy density of the battery.
Smart Images

Figure CN119812446A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application is based on and claims the benefit of priority and all rights arising from Korean Patent Application No. 10-2023-0134364 filed on October 10, 2023, and Korean Patent Application No. 10-2024-0135506 filed on October 7, 2024, in the Korean Intellectual Property Office, the contents of which are incorporated herein in their entirety by reference. Technical Field
[0003] The present disclosure relates to a solid electrolyte, a method of preparing the solid electrolyte, and a secondary battery including the solid electrolyte. Background Art
[0004] The demand for batteries has continued to increase. In addition, as the supply of electric vehicles has accelerated, the demand for batteries has further increased. There are many types of batteries, such as secondary batteries that can be charged and discharged, such as lithium-ion batteries, and primary batteries that can only be discharged. Regardless of the battery type, all of these batteries usually contain electrolytes. Electrolyte leakage, etc. can cause failures in electronic devices. In addition, lithium-ion secondary batteries may have a risk of thermal runaway in particular. In order to solve some of the aforementioned problems, it is still necessary to develop solid batteries using solid electrolytes instead of liquid electrolytes. Summary of the invention
[0005] A solid electrolyte is provided which has improved deformability while having excellent electrochemical stability and ion conductivity (conductivity).
[0006] Provided is a secondary battery having improved battery performance by including the solid electrolyte.
[0007] A method for preparing the solid electrolyte is provided.
[0008] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments of the disclosure.
[0009] According to one aspect of the present disclosure, a solid electrolyte includes a metal oxide including lithium, silicon, and boron and a metal including at least one of iron, chromium, lanthanum, or thallium. The solid electrolyte has a glass structure including 60 mol % or more of lithium relative to a total amount of 100 mol % of the metal and lithium, silicon, and boron. The solid electrolyte has a softness of 152 1 / BHN or more, wherein 1 / BHN is the reciprocal of a Brinell hardness value as measured according to ISO 6506.
[0010] The solid electrolyte may have an ionic conductivity at 60 °C of from about 1 x 10 -6 Siemens / cm (S / cm) to about 5 x 10 -6 S / cm.
[0011] The metal oxide may be an oxide represented by Formula 1.
[0012] Formula 1
[0013] Li a B b Si c M d O e
[0014] In Formula 1, M may be at least one metal and is at least one of iron (Fe), chromium (Cr), lanthanum (La), or thallium (Tl), 0.6 ≤ a ≤ 0.8, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.19, 0.01 ≤ d ≤ 0.04, and 0 < e ≤ 1, where the sum of a, b, c, and d may be 1.
[0015] In one aspect, in Formula 1, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1.
[0016] According to another aspect of the present disclosure, a secondary battery includes: a positive electrode; a negative electrode current collector; and an electrolyte disposed between the positive electrode and the negative electrode current collector, wherein at least one of the positive electrode or the electrolyte may include the solid electrolyte.
[0017] The positive electrode may include a solid electrolyte, and the solid electrolyte may include a metal oxide including at least one of iron (Fe), chromium (Cr), lanthanum (La), or thallium (Tl), and further including lithium (Li), silicon (Si), and boron (B). The solid electrolyte may have a glass structure including 60 mole percent (mol%) or more of lithium, relative to a total of 100 mol% of the metal, lithium, silicon, and boron. The solid electrolyte may have a softness of 152 1 / BHN or greater, where 1 / BHN is the reciprocal of the Brinell hardness value measured according to ISO 6506. As used herein, "glass structure" refers to a material (i.e., glass) having a highly disordered amorphous (non-crystalline) structure. Typically, glass is a material that has been hardened and solidified without crystallization.
[0018] The first negative electrode active material layer may be disposed between the negative electrode current collector and the electrolyte. The first negative electrode active material layer may include one or more of a negative electrode active material containing carbon, a second metal negative electrode active material, or a second metalloid negative electrode active material, wherein the negative electrode active material containing carbon may include amorphous carbon, crystalline carbon, porous carbon, or a combination thereof, and the second metal negative electrode active material or the second metalloid negative electrode active material may include gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof.
[0019] According to one aspect of the present disclosure, a method for preparing a solid electrolyte includes mixing a precursor containing at least one of iron (Fe), chromium (Cr), lanthanum (La), or thallium (Tl), a lithium precursor, a silicon precursor, a boron precursor, and a solvent to obtain a mixture; performing a first heat treatment on the mixture to provide a first heat-treated mixture; performing a second heat treatment on the first heat-treated mixture to provide a product; and quenching the product to provide the solid electrolyte.
[0020] During the quenching, the cooling rate may be about 10 2 Kelvin / second (K / s) to about 10 5 K / s.
[0021] The precursor containing at least one of iron (Fe), chromium (Cr), lanthanum (La), or thallium (Tl) may include Fe 2 O 3 Cr 2 O 3 ,La 2 O 2 , or Tl 2 O 3 At least one of the lithium precursors may include Li 2 O. Li 2 CO 3 、LiCl、LiNO 3 , or Li(OH), the silicon precursor may include tetraethyl orthosilicate or SiO 2 At least one of: 3 BO 3 or B 2 O 3 At least one of.
[0022] Prior to the first heat treatment, drying the mixture may be further performed to provide a dried mixture, wherein the drying may include drying at a temperature of about 50°C to about 90°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The above and other aspects, features and advantages of some embodiments of the present disclosure will become more apparent from the following description considered in conjunction with the accompanying drawings, in which:
[0024] Figure 1 To illustrate a graph of intensity (arbitrary unit, au) versus diffraction angle (degree, 2θ), which shows the results of X-ray diffraction analysis using CuKα radiation for the solid electrolytes prepared in Examples 1 to 4 and Comparative Examples 1 and 2;
[0025] Figure 2 To illustrate the softness (reciprocal of the Brinell hardness value, 1 / BHN) and ionic conductivity [10 -6 Siemens / cm (S / cm)];
[0026] Figures 3 to 6 is a schematic diagram of an embodiment of a lithium secondary battery;
[0027] Figure 7 is a cross-sectional view of an embodiment of the structure of an all-solid-state battery;
[0028] Figure 8 is a cross-sectional view of an embodiment of the structure of an all-solid-state battery;
[0029] Fig. 9 is a cross-sectional view of an embodiment of the structure of an all-solid-state battery;
[0030] Fig.10 is a cross-sectional view of an embodiment of a structure of a multilayer ceramic battery;
[0031] Fig.11 is a cross-sectional view of an embodiment of a structure of a multilayer ceramic battery; and
[0032] Fig.12 is a cross-sectional view of an embodiment of the structure of a multilayer ceramic battery. DETAILED DESCRIPTION
[0033] Embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals refer to the same elements throughout. In this regard, the present embodiment may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the following only describes the embodiments to illustrate aspects by reference to the accompanying drawings. As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. Statements such as "at least one (kind)" when before or after a list of elements modify the entire list of elements and do not modify a single element of the list.
[0034] The inventive concept, which will be described more fully below, may have multiple variations and multiple embodiments, and specific embodiments will be shown in the accompanying drawings and described in more detail. However, the inventive concept should not be construed as being limited to the specific embodiments set forth herein. On the contrary, these embodiments will be construed as covering all variations, equivalents, or substitutes included within the scope of the inventive concept.
[0035] The terms used hereinafter are only used for the purpose of describing specific embodiments, and are not intended to limit the inventive concept. As used herein, the singular form is also intended to include the plural form, unless the context clearly indicates otherwise. As used herein, the term "comprising" or "including" indicates that there are stated features, regions, entireties, steps, operations, elements, components, ingredients, materials, or combinations thereof, but does not exclude the presence or addition of one or more other features, regions, entireties, steps, operations, elements, components, ingredients, materials, or combinations thereof. As used herein, " / " may be interpreted as "and" or "or" depending on the context.
[0036] In the accompanying drawings, for clarity of description, the thickness of layers and regions may be magnified. The same reference numerals represent the same elements throughout the specification. Throughout the specification, when a component such as a layer, film, region, or plate is described as "above" or "on" another component, the component may be directly above the other component, or another component may exist therebetween. It will be understood that although the terms "first", "second", etc. may be used to describe different elements in this article, these elements should not be limited by these terms. These terms are only used to distinguish an element from other elements.
[0037] The term used herein is only used for the purpose of describing specific embodiments and is not intended to be restrictive. As used herein, "one (kind) (indefinite article) (a, an)", "said (the)", and "at least one (kind)" do not represent the limitation of quantity, and are intended to include both the singular and the plural, unless the context clearly indicates otherwise. For example, "element" has the same meaning as "at least one element", unless the context clearly indicates otherwise. "At least one (kind)" will not be interpreted as limiting "one (kind)". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. It will be further understood that the term "comprising" or "including" when used in this specification, indicates that there are stated features, regions, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or its set.
[0038] In addition, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another element as shown in the figure. It will be understood that in addition to the directions shown in the figures, relative terms are also intended to cover different directions of the device. For example, if the device in one of the figures is turned over, the element described as being "on the "lower" side of the other element will be oriented on the "upper" side of the other element. Therefore, the term "lower" may cover both "lower" and "upper" directions depending on the specific direction of the figure. Similarly, if the device in one of the figures is turned over, the element described as being "below" or "below" the other element will be oriented "above" the other element. Therefore, the term "below..." or "below..." may cover both "above..." and "below..." directions.
[0039] As used herein, "about" or "approximately" is inclusive of the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, 20%, 10%, or 5% relative to the stated value.
[0040] Unless otherwise defined, all terms (including technical and scientific terms) used in this article have the same meaning as commonly understood by ordinary technicians in the field to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and the present disclosure, and will not be interpreted in an idealized or overly formal sense unless clearly defined in this article.
[0041] Embodiments are described herein with reference to cross-sectional views as schematic diagrams of idealized embodiments. Thus, deviations from the shapes of the figures as a result of, for example, manufacturing techniques and / or tolerances are to be expected. Therefore, the embodiments described herein should not be construed as being limited to the specific shapes of the regions as illustrated herein, but rather include deviations in shape caused by, for example, manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. In addition, the illustrated sharp corners may be rounded. Therefore, the regions illustrated in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shapes of the regions and are not intended to limit the scope of the claims.
[0042] The term "combination thereof" as used herein may mean a mixture, a stack, a composite, a copolymer, an alloy, a reaction product, etc. of the referred objects.
[0043] The term "metal" as used herein refers to both metals and metalloids in the elemental or ionic state such as silicon and germanium.
[0044] As used herein, the term “positive electrode active material” refers to a positive electrode material capable of undergoing lithiation and delithiation, and the term “negative electrode active material” refers to a negative electrode material capable of undergoing lithiation and delithiation.
[0045] As used herein, the term “lithiation” refers to a process of adding lithium to a positive electrode active material or a negative electrode active material, and the term “delithiation” refers to a process of removing lithium from a positive electrode active material or a negative electrode active material.
[0046] As used herein, the term "charge" refers to a process of supplying electrochemical energy to a battery, and the term "discharge" refers to a process of removing electrochemical energy from a battery.
[0047] As used herein, the terms "positive electrode" and "positive electrode" refer to the electrode at which electrochemical reduction and lithiation occur during the discharge process, and the terms "negative electrode" and "negative electrode" refer to the electrode at which electrochemical oxidation and delithiation occur during the discharge process.
[0048] The term "particle diameter" of a particle as used herein refers to the average diameter if the particle is spherical, and refers to the average major axis length if the particle is non-spherical. The particle diameter of a particle can be measured using a particle size analyzer (PSA). The term "particle diameter" of a particle as used herein refers to, for example, the average particle diameter. Unless otherwise expressly indicated, the average particle diameter refers to the median particle diameter (D50). The median particle diameter (D50) refers to the size of the particle corresponding to the cumulative value of 50% when counting from the minimum particle size on a particle size distribution curve in which particles are accumulated from the minimum particle size to the maximum particle size. The cumulative value can be, for example, a cumulative volume. The median particle diameter (D50) can be measured, for example, by a laser diffraction method.
[0049] If measured using a scanning electron microscope, the size of the particles can be determined as the average of the particle diameters of 30 or more randomly selected particles of 1 µm or greater diameter, excluding fine particles.
[0050] The average particle diameter of the positive electrode active material can be measured using a laser diffraction method. More specifically, the positive electrode active material can be dispersed in a solution and introduced into a commercial laser diffraction particle size measuring device (e.g., Microtrac MT3000) to undergo ultrasonic radiation at a power output of about 28 kilohertz (kHz) and 60 watts, and the average particle diameter (D50) can be calculated based on 50% of the particle size distribution according to the measuring device.
[0051] The term "D10" as used herein may refer to the average diameter of particles corresponding to the cumulative 10 volume percent (vol %) in the particle size distribution, and the term "D90" as used herein may refer to the average diameter of particles corresponding to the cumulative 90 volume % in the particle size distribution.
[0052] A solid electrolyte, a method of preparing the same, and a secondary battery including the same according to an embodiment will be described in more detail below.
[0053] All-solid batteries using solid electrolytes can reduce the risk of leakage or thermal runaway and degradation of battery performance through corrosion, etc. In addition, since some solid electrolytes can provide a wider electrochemical potential window compared to liquid electrolytes, such solid electrolytes can be used to provide batteries with high energy density.
[0054] Among solid electrolytes used in lithium batteries, inorganic solid electrolytes can be classified into ceramic solid electrolytes and glass solid electrolytes. Ceramic solid electrolytes may have excellent lithium ion conductivity, but require high temperature heat treatment for crystallization.
[0055] On the other hand, glass solid electrolytes have received much attention due to their superior mechanical properties compared to ceramic solid electrolytes while having excellent lithium ion conductivity.
[0056] For example, although Li-B-Si based glass electrolytes have excellent mechanical properties, they generally require further improved mechanical properties at low temperatures to provide lithium batteries that can suitably accommodate volume changes during charge and discharge.
[0057] The solid electrolyte according to the embodiment may include a metal oxide including lithium, silicon, and boron and a metal including at least one of iron, chromium, lanthanum, or thallium. The solid electrolyte may have a glass structure including 60 mole percent (mol %) or more of lithium, relative to 100 mol % of the total amount of the metal and lithium, silicon, and boron.
[0058] The solid electrolyte may have excellent lithium ion conductivity and excellent stability, and the solid electrolyte may have a softness of 152 1 / BHN or more, where 1 / BHN is the reciprocal of the Brinell hardness value. If the solid electrolyte has a softness within the aforementioned range, the solid electrolyte may be easily formed into a thin film. Such a solid electrolyte may be a glass phase electrolyte having improved low temperature formability by doping a metal into a Li-B-Si-O (LBSO) oxide electrolyte.
[0059] The solid electrolyte according to the embodiment may be a solid electrolyte that can be formed at low temperatures, which has a glass structure, the glass structure containing 60 mol% or more of lithium, relative to the total amount of 100 mol% of the metal and lithium (Li), silicon (Si), and boron (B), and the solid electrolyte may include a metal oxide, the metal oxide includes at least one of iron (Fe), chromium (Cr), lanthanum (La), or thallium (Tl), and also includes lithium (Li), silicon (Si), and boron (B), wherein the solid electrolyte may have a softness of 152 1 / BHN or more.
[0060] The high concentration of lithium oxide may interfere with obtaining a metal oxide with a glass phase. However, the solid electrolyte containing oxide according to the embodiment may have a glass phase structure with 60 mol % or more of lithium, and by doping at least one of iron (Fe), chromium (Cr), lanthanum (La), or thallium (Tl) in the metal oxide, a solid electrolyte containing oxide with a glass phase may be obtained. Due to the amorphous phase, such a solid electrolyte containing oxide may be formable at low temperatures and have excellent ionic conductivity. In addition, the low temperature may be, for example, 350°C or more, such as a temperature of about 350°C to about 500°C. In addition, compared with glass oxide, the oxide with a glass-ceramic phase may have reduced formability at low temperatures. For example, the low temperature may be, for example, 350°C or more, such as a temperature of about 350°C to about 500°C.
[0061] If the amount of lithium in the solid electrolyte containing the oxide is less than 60 mol %, an amorphous oxide may be easily achieved, but achieving target ion conductivity may be difficult.
[0062] If the solid electrolyte has a softness of less than 152 1 / BHN, the solid electrolyte may have poor deformability, and thus, its low-temperature formability may fail to reach a satisfactory level.
[0063] The amount of lithium in the metal oxide may be 60 mol% or more, about 60 mol% to about 73 mol%, about 60 mol% to about 72 mol%, about 62 mol% to about 70 mol%, or about 62 mol% to about 68 mol%, relative to the total amount of the metal and lithium, silicon, and boron. If the amount of lithium is 60 mol% or more, a solid electrolyte having excellent low temperature formability and excellent ionic conductivity can be prepared.
[0064] The amount of the metal (M) in the metal oxide may be 4 mol% or less, about 1 mol% to about 4 mol%, about 1 mol% to about 3 mol%, about 1 mol% to about 2 mol%, about 1 mol% to about 1.8 mol%, about 1 mol% to about 1.6 mol%, about 1 mol% to about 1.5 mol%, about 1 mol% to about 1.4 mol%, about 1 mol% to about 1.3 mol%, or about 1 mol% to about 1.2 mol%. If the amount of the metal (M) in the metal oxide is 4 mol% or less, the solubility of lithium in the metal oxide may be increased, which thus leads to a suitable increase in ionic conductivity and an increase in deformability of the oxide-containing solid electrolyte.
[0065] The amount of boron in the metal oxide may be about 20 mol % to about 60 mol %, about 20 mol % to about 50 mol %, about 20 mol % to about 40 mol %, or about 20 mol % to about 35 mol %. In addition, the amount of silicon in the metal oxide may be about 0.1 mol % to about 40 mol %, about 0.1 mol % to about 30 mol %, about 0.1 mol % to about 20 mol %, about 0.1 mol % to about 10 mol %, or about 0.1 mol % to about 5 mol %. If the respective amounts of boron and silicon in the metal oxide are within the aforementioned ranges, the solid electrolyte containing the oxide can maintain a glass phase and thus can maintain excellent low temperature formability.
[0066] In the oxide-containing solid electrolyte, the amount of lithium, the amount of metal, the amount of boron, and the amount of silicon can be measured using inductively coupled plasma atomic emission spectrometry (ICP-AES) or the like.
[0067] The solid electrolyte according to the embodiment may have excellent stability for lithium metal. In addition, due to the low glass transition temperature, if the solid electrolyte is mixed with an electrode active material to provide a mixture and then the mixture is hot pressed at a temperature greater than the glass transition temperature of the metal oxide, the solid electrolyte may provide improved wettability to the electrode active material. As described above, due to the low glass transition temperature, the metal oxide according to the embodiment can be used to prepare a positive electrode with excellent physical properties at a low co-sintering temperature.
[0068] The solid electrolyte according to an embodiment may have a glass transition temperature of about 250°C to about 500°C, about 250°C to about 450°C, about 270°C to about 400°C, about 280°C to about 350°C, for example, about 290°C to about 320°C.
[0069] As described above, since the metal oxide included in the solid electrolyte according to the embodiment has a glass transition temperature of 500 ° C or less, when such a solid electrolyte containing oxide is used to sinter the laminate to manufacture a lithium battery, the sintering temperature can be set to 500 ° C or less, and as a result, a wider range of materials can become available for forming positive and negative electrode layers. For example, if a carbon-containing component is used as a material for forming the positive and / or negative electrode layers and the sintering temperature is high, there may be a loss of the carbon-containing component, which may lead to a reduction in energy density. Therefore, if such a carbon-containing component is used as a material for forming an electrode layer, sintering at a low sintering temperature can prevent or minimize the loss of the carbon-containing component.
[0070] The solid electrolyte containing glass oxide according to the embodiment can be confirmed by X-ray diffraction (XRD) analysis. The solid electrolyte containing glass ceramic phase oxide can be distinguished by transmission electron microscopy (TEM) analysis by ring patterns (glass) and dot patterns (ceramic) in TEM images, while the solid electrolyte containing glass phase oxide is confirmed by the absence of such dot patterns typically observed in glass ceramic phase oxides.
[0071] In the XRD spectrum of the electrolyte, the peak intensity (I b ) for the peak intensity (I a ) peak intensity ratio (I b / I a ) may be 3.0 or less, about 0.001 to about 3.0, for example, about 0.01 to about 3.0. The peak at a diffraction angle of 13°2θ±1.0°2θ refers to Figure 1 The peak at a diffraction angle of 13°2θ±1.0°2θ of the oxide of Comparative Example 2, and the peak at a diffraction angle of 5.0°2θ to 9.0°2θ refer to Figure 1 The peak of the oxide of Comparative Example 1 in the diffraction angle range of 5.0°2θ to 9.0°2θ. Using a peak intensity ratio (I b / I a ) can provide improved ionic conductivity.
[0072] X-ray diffraction analysis of the oxide of the solid electrolyte according to the embodiment shows the absence of peaks at diffraction angles of 13° 2θ ± 1.0° 2θ and at diffraction angles of 5.0° 2θ to 9.0° 2θ.
[0073] The solid electrolyte according to the embodiment may have 1 x 10 -7 S / cm or greater, 1 x 10-6 S / cm or greater, or about 1 x 10 -6 S / cm to about 5 x 10 -6 S / cm of ionic conductivity at 60 °C. Due to the increased ionic conductivity within the aforementioned range, the solid electrolyte including the oxide represented by Formula 1 can be used as an electrolyte in a secondary battery.
[0074] The metal oxide according to an embodiment can be the oxide represented by Formula 1.
[0075] Formula 1
[0076] Li a B b Si c M d O e
[0077] In Formula 1, M can be at least one metal and is at least one of iron (Fe), chromium (Cr), lanthanum (La), or thallium (Tl), 0.6 ≤ a ≤ 0.8, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.19, 0.01 ≤ d ≤ 0.04, and 0 < e ≤ 1, where the sum of a, b, c, and d can be 1.
[0078] In one aspect, in Formula 1, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1. For example, 0.2 ≤ b ≤ 0.3 and 0.01 ≤ c ≤ 0.045.
[0079] The oxide of Formula 1 can be at least one of the oxides of Formulas 2 to 5.
[0080] Formula 2
[0081] Li a B b Si c Fe d O e
[0082] In Formula 2, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1, where the sum of a, b, c, and d can be 1,
[0083] Formula 3
[0084] Li a B b Si c Cr d O e
[0085] In Formula 3, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1, where the sum of a, b, c, and d can be 1.
[0086] Formula 4
[0087] Li a B b Si c La d O e
[0088] In Formula 4, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1, where the sum of a, b, c, and d can be 1.
[0089] Formula 5
[0090] Li a B b Si c Tl d O e
[0091] In Formula 5, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1, where the sum of a, b, c, and d can be 1.
[0092] In one aspect, in Formulas 2 to 5, 0.2 ≤ b ≤ 0.3 and 0.01 ≤ c ≤ 0.045.
[0093] The oxide can be Li 0.625 B 0.321 Si 0.044 Fe 0.010 O 1-σ 、Li 0.625 B 0.321 Si 0.044 Cr 0.010 O 1-σ 、Li 0.625 B 0.321 Si 0.044 La 0.010 O 1-σ 、Li 0.625 B 0.321 Si 0.044 Tl 0.010 O 1-σ 、or a combination thereof, where σ renders the charge state of the oxide neutral, where 0 ≤ σ < 1.
[0094] The softness (1 / BHN) of the solid electrolyte may be about 152 1 / BHN to about 260 1 / BHN, about 160 1 / BHN to about 255 1 / BHN, about 170 1 / BHN to about 250 1 / BHN, about 180 1 / BHN to about 252 1 / BHN, or about 187 1 / BHN to about 255 1 / BHN. The softness may be the reciprocal of the Brinell hardness value as measured by the Brinell hardness test method, and for details, reference is made to the description provided in the evaluation examples below. The Brinell hardness test may be performed according to ISO 6506.
[0095] As described above, the solid electrolyte according to the embodiment may have improved deformable properties and may be formed into various shapes at low temperatures. In addition, since it is formable at low temperatures, the solid electrolyte may reduce the deformation of a structure such as an electrode combined therewith, and may stabilize the interface properties between the solid electrolyte and the structure.
[0096] A solid electrolyte containing a metal oxide represented by Formula 1 can promote lithium transfer. In addition, the solid electrolyte may have a thickness of about 0.1 micrometers (µm) to about 500 µm, about 1 µm to about 200 µm, about 5 µm to about 200 µm, for example, about 5 µm to about 80 µm. Using a solid electrolyte having a thickness within the aforementioned range, the solid electrolyte may have excellent mechanical properties such as deformability and improved ion conductivity.
[0097] The solid electrolyte including the compound represented by Formula 1 is not limited to any particular form. The solid electrolyte including the compound represented by Formula 1 may have, for example, a particle form. The particle form may be a spherical particle or a non-spherical particle. The solid electrolyte in particle form may be formed into a variety of forms (shapes). The shaped solid electrolyte may be in the form of, for example, a sheet.
[0098] The secondary battery may be, for example, a lithium battery.
[0099] Lithium battery
[0100] A lithium battery according to another embodiment may include: a positive electrode; a negative electrode; and an electrolyte disposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode, the negative electrode, or the electrolyte may include the solid electrolyte described above. The aforementioned solid electrolyte may include a compound represented by Formula 1. Since the lithium battery contains the aforementioned solid electrolyte, the internal resistance of the lithium battery may be reduced and the cycle performance of the lithium battery may be improved. The lithium battery is not limited to any particular type, and may be, for example, a lithium ion battery, an all-solid battery, a multilayer ceramic (MLC) battery, a lithium-air battery, and the like.
[0101] According to an embodiment, the cathode may include, for example, a solid electrolyte according to an embodiment.
[0102] If a lithium battery is manufactured using the solid electrolyte according to the embodiment, highly uniform interface characteristics between the solid electrolyte and the positive electrode may be ensured.
[0103] The electrolyte of the lithium battery may be, for example, a liquid electrolyte, a solid electrolyte, a gel electrolyte, or a combination thereof.
[0104] In one or more embodiments, the electrolyte may be an organic electrolyte. The organic electrolyte may be prepared, for example, by dissolving a lithium salt in an organic solvent.
[0105] For the organic solvent, any organic solvent available in the art can be used. The organic solvent can be, for example, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, and a mixture thereof.
[0106] The lithium salt may be any lithium salt available in the art. The lithium salt may be, for example, LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiCF 3 SO 3 、Li(CF 3 SO 2 ) 2 N、Li(FSO 2 ) 2 N, LiC 4 F 9 SO 3 、LiAlO 2 、LiAlCl 4 、LiN(C x F 2x+1 SO 2 )(C y F 2y+1 SO 2(1 ≤ x ≤ 20, 1 ≤ y ≤ 20), LiCl, LiI, or a mixture thereof. The concentration of the lithium salt can be, for example, from about 0.1 moles per liter (M) to about 5.0 M.
[0107] Examples of the solid electrolyte include oxide solid electrolytes, sulfide solid electrolytes, polymer solid electrolytes, or combinations thereof.
[0108] The solid electrolyte can be, for example, an oxide solid electrolyte. The oxide solid electrolyte can be one or more selected from the following: Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 < x < 2 and 0 ≤ y < 3), BaTiO 3 , Pb(Zr a Ti 1-a )O 3 (“PZT”, 0 ≤ a ≤ 1), Pb 1-x La x Zr 1-y Ti y O 3 (“PLZT”) (0 ≤ x < 1 and 0 ≤ y < 1), Pb(Mg 1 / 3 Nb 2 / 3 )O 3 -PbTiO 3 (“PMN-PT”), HfO 2 、SrTiO 3 、SnO 2 、CeO 2 、Na 2 O, MgO, NiO, CaO, BaO, ZnO, ZrO 2 、Y 2 O 3 、Al 2 O 3 、TiO 2 、SiO 2 、Li 3 PO 4 、Li x Ti y (PO 4 ) 3 (0 < x < 2 and 0 < y < 3), Li x Al y Ti z (PO 4 ) 3 (0 < x < 2, 0 < y < 1, and 0 < z < 3), Li 1+x+y (Ala Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P 3-y O 12 (0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ a ≤ 1, and 0 ≤ b ≤ 1), Li x La y TiO 3 (0 < x < 2 and 0 < y < 3), Li 2 O, LiOH, Li 2 CO 3 、LiAlO 2 、Li 2 O - Al 2 O 3 - SiO 2 - P 2 O 5 - TiO 2 - GeO 2 、和Li 3+x La 3 M 2 O 12 (M is Te, Nb, or Zr, and x is an integer from 1 to 10). The solid electrolyte can be manufactured by a method such as a sintering method. For example, the oxide solid electrolyte can be a garnet solid electrolyte selected from Li 7 La 3 Zr 2 O 12 (“LLZO”) and Li 3+ x La 3 Zr 2-a M a O 12 (“M - doped LLZO”, M is Ga, W, Nb, Ta, or Al, 0 < a < 2, and x is an integer from 1 to 10). As used herein, garnet is a silicate represented by the formula X 3 Y 2 (SiO 4 ) 3 where X is a divalent cation and Y is a trivalent cation. As used herein, the term “garnet solid electrolyte” means that the solid electrolyte is related to garnet such as Mg 3 Al 2 (SiO 4 ) 3Isomorphic. In the present disclosure, the term "isomorphic" refers to the crystal structure of a compound. The crystal structures are the same, but the unit cell dimensions and / or chemical compositions may be different.
[0109] Examples of the sulfide solid electrolyte include lithium sulfide, silicon sulfide, phosphorus sulfide, boron sulfide, or a combination thereof. The sulfide solid electrolyte particles may include Li 2 S, P 2 S 5 , SiS 2 , GeS 2 , B 2 S 3 , or a combination thereof. The sulfide solid electrolyte particles may be Li 2 S or P 2 S 5 . It is known that the sulfide solid electrolyte particles have a higher lithium ion conductivity than other inorganic compounds. For example, the sulfide solid electrolyte may include Li 2 S and P 2 S 5 . If the sulfide solid electrolyte material constituting the sulfide solid electrolyte includes Li 2 S-P 2 S 5 , then the mixed molar ratio of Li 2 S to P 2 S 5 may be, for example, in the range of about 50:50 to about 90:10. For example, materials such as Li 3 PO 4 , halogens, halogen compounds, Li 2+2x Zn 1-x GeO 4 (“LISICON”, 0 ≤ x < 1), Li 3+y PO 4-x N x (“LIPON”, 0 < x < 4 and 0 < y < 3), Li 3.25 Ge 0.25 P 0.75 S 4 (“Thio-LISICON”), and Li 2 O-Al 2 O 3 -TiO 2 -P 2 O 5 (“LATP”) can be added to an inorganic solid electrolyte such as Li 2 S-P 2 S 5 , SiS 2 , GeS 2 , B2 S 3 、 or a combination thereof, to prepare an inorganic solid electrolyte, and the inorganic solid electrolyte can be used as a sulfide solid electrolyte. Non-limiting examples of the sulfide solid electrolyte material include Li 2 S-P 2 S 5 ; Li 2 S-P 2 S 5 -LiX (X is a halogen element, such as Cl, Br, or I); Li 2 S-P 2 S 5 -Li 2 O; Li 2 S-P 2 S 5 -Li 2 O-LiI; Li 2 S-SiS 2 ; Li 2 S-SiS 2 -LiI; Li 2 S-SiS 2 -LiBr; Li 2 S-SiS 2 -LiCl; Li 2 S-SiS 2 -B 2 S 3 -LiI; Li 2 S-SiS 2 -P 2 S 5 -LiI; Li 2 S-B 2 S 3 ; Li 2 S -P 2 S 5 -Z m S n (0 < m < 10, 0 < n < 10, and Z is Ge, Zn or Ga); Li 2 S-GeS 2 ; Li 2 S-SiS 2 -Li 3 PO 4 ; and Li 2 S-SiS 2 -Li p MO q(0 < p < 10, 0 < q < 10, and M is P, Si, Ge, B, Al, Ga, or In). In this regard, the sulfide solid electrolyte material can be prepared by, for example, subjecting starting materials of the sulfide solid electrolyte material (e.g., Li 2 S, P 2 S 5 etc.) to processes such as melt quenching, mechanical grinding, etc. Additionally, a calcination process can be performed after the above processes. The sulfide solid electrolyte can be amorphous, crystalline, or in a mixed state between amorphous and crystalline.
[0110] For example, the polymer solid electrolyte can include a mixture of a lithium salt and a polymer, or can include a polymer having an ion-conducting functional group. For example, the polymer solid electrolyte can be a polymer electrolyte that is in a solid state at 25°C and 1 atmosphere (atm). For example, the polymer solid electrolyte can be free of liquid. The polymer solid electrolyte can include a polymer. For example, the polymer can be polyethylene oxide (“PEO”), polyvinylidene fluoride (“PVDF”), polyvinylidene fluoride - hexafluoropropylene (“PVDF - HFP”), poly(styrene - b - ethylene oxide) block copolymer (“PS - PEO”), poly(styrene - butadiene), poly(styrene - isoprene - styrene), poly(styrene - b - divinylbenzene) block copolymer, poly(styrene - ethylene oxide - styrene) block copolymer, polysulfonated styrene (“PSS”), polyvinyl fluoride (“PVF”), poly(methyl methacrylate) (“PMMA”), polyethylene glycol (“PEG”), polyacrylonitrile (“PAN”), polytetrafluoroethylene (“PTFE”), polyethylenedioxythiophene (“PEDOT”), polypyrrole (“PPY”), polyaniline, polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, sulfonated poly(ether ether ketone) (“SPEEK”), sulfonated poly(arylene ether ketone ketone sulfone) (“SPAEKKS”), sulfonated poly(aryl ether ketone) (“SPAEK”), poly[bis(benzimidazole benzoisoquinolinone)] (“SPBIBI”), or a combination thereof. However, the polymer is not limited to the foregoing examples and can be any material available in the art for use in polymer electrolytes. For example, the polymer included in the polymer solid electrolyte can be a compound having 10 or more repeating units, 20 or more repeating units, 50 or more repeating units, or 100 or more repeating units. For example, the polymer included in the polymer solid electrolyte can have a weight-average molecular weight of 1,000 daltons or greater, 10,000 daltons or greater, 100,000 daltons or greater, or 1,000,000 daltons or greater.
[0111] The gel electrolyte may be, for example, a polymer gel electrolyte. For example, the gel electrolyte may have a gel state while not containing a polymer.
[0112] For example, the polymer gel electrolyte may include a liquid electrolyte and a polymer, or may include an organic solvent and a polymer having an ion-conducting functional group. The polymer gel electrolyte may be, for example, a polymer electrolyte in a gel state at 25°C and 1 atm. For example, the polymer gel electrolyte may have a gel state without containing a liquid. The liquid electrolyte used in the polymer gel electrolyte may be, for example, a mixture of an ionic liquid, a lithium salt, and an organic solvent; a mixture of a lithium salt and an organic solvent; a mixture of an ionic liquid and an organic solvent; or a mixture of a lithium salt and an ionic liquid. The polymer used in the polymer gel electrolyte may be selected from polymers used in solid polymer electrolytes. The organic solvent may be selected from organic solvents used in liquid electrolytes. The lithium salt may be selected from lithium salts used in the polymer solid electrolyte. An ionic liquid may refer to a room temperature molten salt or a salt in a liquid state at room temperature, which is composed only of ions and has a melting point at room temperature or less. For example, the ionic liquid may be at least one selected from compounds containing the following: a) at least one cation as follows: ammonium, pyrrolidine, , pyridine , pyrimidine Imidazole , piperidine Pyrazole , Azoles Pyridazine , , sulfonium, triazole , or a mixture thereof; and b) at least one anion as follows: BF 4 - PF 6 - , AsF 6 - , SbF 6 - 、AlCl 4 - , HSO 4 - , ClO 4 - , CH 3 SO 3 - CF 3 CO 2 - , Cl - Br - ,I- 、SO 4 2- CF 3 SO 3 - 、(FSO 2 ) 2 N - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 )(CF 3 SO 2 )N - , or (CF 3 SO 2 ) 2 N - . For example, the polymer solid electrolyte may form a polymer gel electrolyte by being immersed in a liquid electrolyte in a secondary battery. The polymer gel electrolyte may further include inorganic particles. For example, the polymer included in the polymer gel electrolyte may be a compound containing 10 or more repeating units, 20 or more repeating units, 50 or more repeating units, or 100 or more repeating units. For example, the polymer included in the polymer gel electrolyte may have a weight average molecular weight of 500 Daltons or more, 1,000 Daltons or more, 10,000 Daltons or more, 100,000 Daltons or more, or 1,000,000 Daltons or more.
[0113] The lithium battery may be, for example, a lithium ion battery or an all-solid secondary battery.
[0114] These batteries are described in more detail below.
[0115] Lithium-ion battery
[0116] Figures 3 to 6 is a schematic diagram of a lithium ion battery according to an embodiment.
[0117] The lithium ion battery may be, for example, a lithium battery including a liquid electrolyte. The lithium ion battery may include a solid electrolyte according to an embodiment.
[0118] A lithium ion battery may include, for example, a positive electrode containing a positive electrode active material; a negative electrode containing a negative electrode active material; and a liquid electrolyte disposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode may include a solid electrolyte according to an embodiment. A lithium ion battery may include, for example, a positive electrode, a negative electrode, and a liquid electrolyte disposed between the positive electrode and the negative electrode, wherein a protective layer including a solid electrolyte according to an embodiment may be disposed on one side of at least one of the positive electrode and the negative electrode. A lithium ion battery may include, for example, a positive electrode active material layer, wherein the positive electrode active material layer may include a composite positive electrode active material including: a core including a positive electrode active material; and a first coating layer disposed on the core, wherein the first coating layer may include a solid electrolyte according to an embodiment. A lithium ion battery may include, for example, a negative electrode active material layer, wherein the negative electrode active material layer may include a composite negative electrode active material including: a core including a negative electrode active material; and a second coating layer disposed on the core, wherein the second coating layer may include a solid electrolyte according to an embodiment.
[0119] For example, a lithium ion battery can be prepared as follows.
[0120] First, a positive electrode can be prepared. A positive electrode active material composition can be prepared by mixing a positive electrode active material, a conductive material, a binder, and a solvent. A positive electrode can be prepared by directly applying and drying the positive electrode active material composition on a positive electrode current collector. Alternatively, a positive electrode can be prepared by casting the positive electrode active material composition on a separate carrier, and then laminating the film peeled off from the carrier on a positive electrode current collector. Alternatively, the positive electrode active material composition can be prepared as an electrode ink containing an excess solvent, and then printed on a carrier by an inkjet method or a gravure printing method to thereby prepare a positive electrode. The printing method is not limited to the aforementioned method, and may be any method that can be used for general coating and printing.
[0121] The solid electrolyte according to the embodiment may be applied to one surface of the positive electrode active material layer included in the positive electrode to thereby form a positive electrode protective layer. Alternatively, the solid electrolyte particles according to the embodiment may be added to the positive electrode active material layer composition and thus included in the positive electrode active material layer.
[0122] The positive electrode current collector may utilize, for example, a plate, foil, etc. formed of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof.
[0123] The positive electrode current collector may include, for example, a base film and a metal layer disposed on one or both sides of the base film. For example, the base film may include a polymer. For example, the polymer may include polyethylene terephthalate ("PET"), polyethylene ("PE"), polypropylene ("PP"), polybutylene terephthalate ("PBT"), polyimide ("PI"), or a combination thereof. For example, the base film may be an insulator. Since the base film includes an insulating thermoplastic polymer, in the case of a short circuit, the base film softens or liquefies, preventing the operation of the battery to thereby prevent a rapid increase in current. For example, the metal layer may include indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. In the case of an overcurrent, the metal layer may be disconnected, thereby acting as an electrochemical fuse to provide protection against a short circuit. By controlling the thickness of the metal layer, the limiting current and the maximum current can be controlled. The metal layer may be plated or deposited on the base film. Since the limiting current and / or maximum current of the positive electrode collector 11 are reduced if the thickness of the metal layer is reduced, the stability of the lithium battery during short circuit can be improved. A lead tab may be added to the metal layer for connection to the outside. The lead tab may be welded to the metal layer or the metal layer / base film laminate by ultrasonic welding, laser welding, spot welding, etc. Since the base film and / or the metal layer melts during welding, the metal layer may be electrically connected to the lead tab. In order to provide a stronger weld between the metal layer and the lead tab, a metal substrate (chip) may be added between the metal layer and the lead tab. The metal substrate may be a thin sheet (scale) of the same material as the metal of the metal layer. For example, the metal substrate may be a metal foil, a metal mesh, etc. For example, the metal substrate may be an aluminum foil, a copper foil, a SUS foil, etc. By welding the metal layer with the lead tab after the metal substrate is placed on the metal layer, the lead tab can be welded to the metal substrate / metal layer laminate or the metal substrate / metal layer / base film laminate. Since the base film, metal layer, and / or metal substrate melt during welding, the metal layer or the metal layer / metal substrate laminate can be electrically connected to the lead tab. The metal substrate and / or the lead tab can be further added to a portion of the metal layer. For example, the base film can have a thickness of about 1 μm to about 50 μm, about 1.5 μm to about 50 μm, about 1.5 μm to about 40 μm, or about 1 μm to about 30 μm. Using a base film with a thickness within the above range, the weight of the electrode assembly can be more effectively reduced.For example, the base film may have a melting point of about 100°C to about 300°C, about 100°C to about 250°C or less, or about 100°C to about 200°C. Since the base film has a melting point in the above range, the base film can be easily melted and bonded to the lead tab when welding the lead tab. In order to improve the adhesion between the base film and the metal layer, the base film may be surface treated such as corona treatment. For example, the metal layer may have a thickness of about 0.01 µm to about 3 µm, about 0.1 µm to about 3 µm, about 0.1 µm to about 2 µm, or about 0.1 µm to about 1 µm. Using a metal layer with a thickness in the above range, the electrode assembly can provide stability while maintaining conductivity. For example, the metal substrate may have a thickness of about 2 µm to about 10 µm, about 2 µm to about 7 µm, or about 4 µm to about 6 µm. With the metal substrate having a thickness within the above range, the metal layer and the lead tab can be connected more easily. With the positive electrode collector 11 having the aforementioned structure, the weight of the electrode can be reduced, and as a result, the energy density of the solid secondary battery can be improved.
[0124] The positive electrode collector may be omitted. The positive electrode collector may further include a carbon layer disposed on one or both sides of the metal substrate. With the carbon layer further disposed on the metal substrate, it may be possible to protect the metal in the metal substrate from corrosion of the solid electrolyte included in the positive electrode layer and reduce the interface resistance between the positive electrode active material layer and the positive electrode collector. The carbon layer may have a thickness of, for example, about 0.1 µm to about 5 µm, about 0.1 µm to about 3 µm, or about 0.1 µm to about 1 µm. If the thickness of the carbon layer is too thin, it may be difficult to completely prevent the metal substrate and the solid electrolyte from contacting each other. If the carbon layer is too thick, the energy density of the all-solid secondary battery may be reduced. The carbon layer may include amorphous carbon, crystalline carbon, and the like.
[0125] As the positive electrode active material, a compound capable of reversible insertion and extraction of lithium (lithiated intercalation compound) may be used. In one or more embodiments, one or more composite oxides of lithium and metals selected from cobalt, manganese, nickel, or a combination thereof may be used.
[0126] The composite oxide may be a lithium transition metal composite oxide, examples of which include lithium nickel oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate compounds, lithium nickel manganese oxide not containing cobalt, or a combination thereof.
[0127] As an example, a compound represented by any one of the following formulae may be used: Li a A 1-b X b O2-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a Mr 2-b X b O 4-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a Ni 1-b-c Co b X c O 2-α D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mr b X c O 2-α D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni b Co c L 1 d G e O 2 (0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0≤e≤0.1);Li a NiG b O 2 (0.90≤a≤1.8,0.001≤b≤0.1);Li a CoG b O 2 (0.90≤a≤1.8,0.001≤b≤0.1);Li a Mr 1-b G b O 2 (0.90≤a≤1.8,0.001≤b≤0.1);Li a Mr 2 G b O 4 (0.90≤a≤1.8,0.001≤b≤0.1);Li a Mr 1-g G g NIGHT 4 (0.90≤a≤1.8,0≤g≤0.5);Li (3-f) Feb 2 (NIGHT 4 ) 3(0≤f≤2); and Li a FePO 4 (0.90≤a≤1.8).
[0128] In the above formula, A may be Ni, Co, Mn, or a combination thereof; X may be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D may be O, F, S, P, or a combination thereof; G may be Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; and L 1 It may be Mn, Al, or a combination thereof.
[0129] As an example, the positive electrode active material may be a high nickel positive electrode active material having a nickel content of 80 mole percent (mol%) or greater, 85 mole % or greater, 90 mole % or greater, 91 mole % or greater, or 94 mole % or greater and 99 mole % or less, relative to 100 mole % of all metals except lithium in the lithium transition metal composite oxide. Due to its ability to achieve high capacity, the high nickel positive electrode active material can be applied to high capacity and high density lithium secondary batteries.
[0130] A positive electrode for a lithium secondary battery may include a current collector and a positive electrode active material layer formed on the current collector. The positive electrode active material layer may include a positive electrode active material, and may further include a binder and / or a conductive material.
[0131] For example, the positive electrode may further include an additive that may serve as a sacrificial positive electrode.
[0132] The conductive material may include, for example, carbon black, carbon fiber, graphite, or a combination thereof. The carbon black may be, for example, acetylene black, Ketjen black, Super P carbon, channel black, furnace black, lamp black, pyrolytic carbon black, or a combination thereof. The graphite may be natural graphite or artificial graphite. A combination containing at least two of the aforementioned conductive materials may be used. The positive electrode may further include an additional conductive material in addition to the aforementioned carbonaceous conductive material. Examples of the additional conductive material include conductive fibers such as metal fibers; fluorinated carbon powder; metal powders such as aluminum powder or nickel powder; conductive whiskers such as zinc oxide and potassium titanate; or polyethylene derivatives. A combination of two or more of the aforementioned conductive materials may be used.
[0133] The binder can improve the adhesion between the positive electrode components and the adhesion of the positive electrode active material layer to the current collector. Examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.
[0134] The amount of the positive active material may be about 90 weight percent (wt %) to about 99.5 wt % relative to 100 wt % of the positive active material layer, and the amount of the binder and the conductive material may be about 0.5 wt % to about 5 wt %, respectively, relative to 100 wt % of the positive active material layer.
[0135] N-methylpyrrolidone, acetone, and / or water may be used as the solvent. The positive electrode active material, conductive material, binder, and solvent may each be used in an amount generally used in a lithium battery.
[0136] By adding a plasticizer to the positive electrode active material composition, pores may be generated in the positive electrode active material layer.
[0137] Next, the negative electrode can be prepared. The negative electrode active material composition can be prepared by mixing the negative electrode active material, the conductive material, the binder, and the solvent. The negative electrode can be prepared by directly applying and drying the negative electrode active material composition on the copper current collector. Alternatively, the negative electrode can be prepared by casting the negative electrode active material composition on a separate carrier, and then peeling the negative electrode active material film from the carrier and stacking it on the copper current collector. Alternatively, the negative electrode active material composition can be prepared as an electrode ink containing an excess solvent, and then printed on the carrier by an inkjet method or a gravure printing method to thereby prepare the negative electrode. Not limited to the aforementioned method, printing can utilize any method that can be used in conventional coating and printing.
[0138] The negative electrode active material may include a material capable of reversible intercalation / deintercalation of lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.
[0139] Examples of materials capable of reversible insertion / deinsertion of lithium ions include negative electrode active materials containing carbon, such as crystalline carbon, amorphous carbon, or a combination thereof. Examples of crystalline carbon include graphite, such as artificial graphite or natural graphite in the form of an unshaped, plate, flake, spherical or fiber. Examples of amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0140] Examples of alloys of lithium metal include alloys of lithium with the following metals: Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, or Sn.
[0141] Examples of the material capable of doping and de-doping lithium include Si negative electrode active material or Sn negative electrode active material. The Si negative electrode active material may be silicon, a silicon-carbon composite, SiO x (0 < x < 2), an Si-Q alloy (where Q is selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof), or a combination thereof. The Sn negative electrode active material may be Sn, SnO 2 , an Sn alloy, or a combination thereof.
[0142] The silicon-carbon composite may be a composite of silicon and amorphous carbon. According to an embodiment, the silicon-carbon composite may be in the form of silicon particles coated with amorphous carbon on the surface of the silicon particles. For example, the silicon-carbon composite may include secondary particles (cores) in which silicon primary particles are aggregated (assembled), and an amorphous carbon coating layer (shell) located on the surface of these secondary particles. The amorphous carbon may also be located between the silicon primary particles, for example, such that the silicon primary particles may be coated with amorphous carbon. The secondary particles may be present while being dispersed in the amorphous carbon matrix.
[0143] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core containing crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core.
[0144] The Si negative electrode active material or the Sn negative electrode active material may be used in a mixture with a negative electrode active material containing carbon.
[0145] The negative electrode for a lithium secondary battery may include a current collector and a negative electrode active material layer located on the current collector. The negative electrode active material layer may include a negative electrode active material, and may further include a binder and / or a conductive material.
[0146] For example, the negative electrode active material layer may include from about 90 wt% to about 99 wt% of a negative electrode active material, from about 0.5 wt% to about 5 wt% of a binder, and from about 0 wt% to about 5 wt% of a conductive material, relative to 100 wt% of the negative electrode active material layer.
[0147] The binder may play a role in ensuring adhesion between negative electrode active material particles and adhesion of the negative electrode active material to the current collector. As the binder, a non-aqueous binder, an aqueous (water-containing) binder, a dry binder, or a combination thereof may be used.
[0148] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or a combination thereof.
[0149] Examples of the aqueous binder include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer (EPDM), polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or a combination thereof.
[0150] If the aqueous binder is used as the negative electrode binder, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or a mixture of one or more of their alkali metal salts may be used. As the alkali metal, Na, K, or Li may be used.
[0151] The dry binder may be, as a fibrillable polymer material, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0152] The conductive material imparts conductivity to the electrode and may be any electron-conducting material that does not cause chemical changes in the battery in which it is to be included. Examples of the conductive material include carbon-containing materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal materials in the form of metal powder or metal fiber containing copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0153] The negative electrode current collector may include a copper foil, a nickel foil, a stainless steel foil, a titanium foil, a nickel foam, a copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0154] The negative electrode current collector may include, for example, a base film and a metal layer disposed on one or both sides of the base film. For example, the base film may include a polymer. For example, the polymer may be a thermoplastic polymer. For example, the polymer may include polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The polymer may be an insulating polymer. Since the base film includes an insulating thermoplastic polymer, in the event of a short circuit, the base film softens or liquefies, preventing the operation of the battery to thereby prevent a rapid increase in current. For example, the metal layer may include copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The negative electrode current collector may further include a metal substrate and / or a lead tab. For details of the base film, metal layer, metal substrate, and lead tab of the negative electrode current collector, refer to the positive electrode current collector 11 described above. Using the negative electrode current collector having the aforementioned structure, the weight of the negative electrode can be reduced, and as a result, the energy density of the solid secondary battery can be improved.
[0155] A protective layer containing a solid electrolyte according to an embodiment may be disposed on one side of the negative electrode active material layer. Alternatively, the negative electrode active material may include negative electrode active material particles, which include: a core containing lithium metal, a lithium metal alloy, or a combination thereof; and a first coating layer disposed on the core, wherein the coating layer may include a solid electrolyte according to an embodiment. With such a protective layer and / or coating layer disposed on the negative electrode, the negative electrode may have improved lithium ion conductivity and / or stability to lithium metal. Alternatively, the solid electrolyte according to an embodiment may be added to the composition forming the negative electrode active material layer and thus included in the negative electrode active material layer.
[0156] Next, a separator may be prepared.
[0157] The positive electrode and the negative electrode may be separated by a separator, wherein the separator may be any separator commonly used in lithium batteries. For the separator, any separator capable of holding a large amount of electrolyte while presenting low resistance to ion migration in the electrolyte may be suitable. For example, the separator may be in the form of a nonwoven or woven fabric formed by a material selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof. In particular, lithium ion batteries may utilize, for example, a reelable separator formed by polyethylene, polypropylene, etc., and lithium ion polymer batteries may utilize, for example, a separator capable of holding a large amount of organic electrolyte.
[0158] The separator can be prepared by the method described below. Once the separator composition is prepared by mixing a polymer resin, a filler, and a solvent, the separator composition can be directly coated and dried on the electrode to form a separator film. Alternatively, the separator can be formed by casting and drying the separator composition on a support, and then laminating the separator film peeled off from the support on the electrode. The polymer resin is not particularly limited, and any material that can be used as a binder for an electrode plate can be used. For example, the polymer resin can utilize a vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, or a mixture thereof. It may be preferred as follows: using a vinylidene fluoride / hexafluoropropylene copolymer having a hexafluoropropylene content of about 8% by weight to about 25% by weight, relative to 100% by weight of the vinylidene fluoride / hexafluoropropylene copolymer.
[0159] The separator may include a porous substrate and a coating layer on one side or both sides of the porous substrate, the coating layer containing an organic material, an inorganic material, or a combination thereof.
[0160] The porous substrate may be a polymer film formed by any of the following polymers: polyolefins such as polyethylene or polypropylene; polyesters such as polyethylene terephthalate or polybutylene terephthalate; polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryletherketone, polyetherimide, polyamide-imide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, Teflon, or polytetrafluoroethylene. In some embodiments, the porous substrate may be a polymer film formed by a copolymer or mixture of two or more of the aforementioned polymers.
[0161] The organic material may include a polyvinylidene fluoride polymer or a (meth)acryl polymer.
[0162] The inorganic material may include, but is not limited to, Al 2 O 3 、SiO 2 、TiO 2 SnO 2 、CeO 2 , MgO, NiO, CaO, GaO, ZnO, ZrO 2 , Y 2 O 3 、SrTiO 3 、BaTiO 3 Mg(OH) 2 , boehmite, or inorganic particles of a combination thereof.
[0163] The organic material and the inorganic material may exist together in a mixed state in one coating layer, or one coating layer including the organic material and another coating layer including the inorganic material may exist in a stacked form.
[0164] The separator may further include a solid electrolyte according to an embodiment. For example, a coating containing a solid electrolyte according to an embodiment may be added to at least one surface of the separator. The separator may include, for example, a porous substrate; and a coating disposed on one or both sides of the porous substrate, wherein the coating may include a solid electrolyte containing a compound represented by Formula 1.
[0165] Next, a liquid electrolyte may be prepared.
[0166] The liquid electrolyte may be an organic electrolyte containing an organic solvent. The organic electrolyte may be prepared by dissolving a lithium salt in an organic solvent. For the organic solvent, any or all organic solvents available in the art may be used. The organic solvent may be, for example, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a mixture thereof. For the lithium salt, any lithium salt available in the art may be used. For example, the lithium salt may be LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiCF 3 SO 3 、Li(CF 3 SO 2 ) 2 N、Li(FSO 2 ) 2 N、Li(FSO 2 ) 2 N, LiC 4 F 9 SO 3 、LiAlO 2 、LiAlCl 4 、LiN(C x F 2x+ 1 SO 2 )(C y F2y+1 SO 2 ) (wherein x and y are different from each other and are each independently an integer of 1-20), LiCl, LiI, or a mixture thereof. The amount of the lithium salt may be from about 0.1 M to about 10 M or from about 0.1 M to about 5 M, but is not necessarily limited to the aforementioned range and may be appropriately adjusted within a range that provides improved battery performance. The liquid electrolyte may further include a flame retardant, such as a phosphorus flame retardant or a halogen flame retardant.
[0167] Lithium secondary batteries may be classified into a cylindrical type, a prismatic type, a pouch type, a coin type, etc., depending on their form. Figures 3 to 6 is a schematic diagram showing a lithium secondary battery according to an embodiment, wherein Figure 3 Display cylindrical battery, Figure 4 A prismatic battery is shown, and Figure 5 and 6 Shows pouch cell battery. Figures 3 to 6 , the lithium secondary battery 100 may include an electrode assembly 40 and a case 50 accommodating the electrode assembly 40, the electrode assembly 40 having a separator 30 disposed between a positive electrode 10 and a negative electrode 20. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated in an electrolyte (not shown). The lithium secondary battery 100 may include a sealing member 60 that seals the case 50, such as Figure 3 In addition, Figure 4 As shown in , the lithium secondary battery 100 may include a positive electrode lead tab 411, a positive electrode terminal 412, a negative electrode lead tab 421, and a negative electrode terminal 422. Figure 5 and 6 As shown in , the lithium secondary battery 100 may include electrode tabs 70 , for example, a positive electrode tab 71 and a negative electrode tab 72 , which serve as electrical paths for guiding current generated at the electrode assembly 40 to the outside.
[0168] The lithium secondary battery according to an embodiment of the present disclosure may be applied to automobiles, mobile phones, and / or various types of electrical devices, but the present disclosure is not limited thereto.
[0169] All-solid-state battery
[0170] The all-solid battery may be, for example, a battery including a solid electrolyte. The all-solid battery may include the solid electrolyte according to the embodiment.
[0171] The all-solid battery may include, for example, a positive electrode containing a positive electrode active material; a negative electrode containing a negative electrode active material; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode, the negative electrode, or the solid electrolyte layer may include a solid electrolyte according to an embodiment. For example, the all-solid battery may include a positive electrode active material layer, wherein the positive electrode active material layer may include a solid electrolyte according to an embodiment. For example, the all-solid battery may include a negative electrode active material layer, wherein the negative electrode active material layer may include a solid electrolyte according to an embodiment. The all-solid battery may include a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the solid electrolyte layer may include a solid electrolyte containing a compound represented by Formula 1. The all-solid battery may include, for example, a positive electrode active material layer, wherein the positive electrode active material layer may include a composite positive electrode active material, which includes: a core including a positive electrode active material; and a first coating layer disposed on the core, wherein the first coating layer may include a solid electrolyte represented by Formula 1. An all-solid battery may include, for example, a negative electrode active material layer, wherein the negative electrode active material layer may include a composite negative electrode active material, which includes: a core including a negative electrode active material; and a second coating layer disposed on the core, wherein the second coating layer may include a solid electrolyte represented by Formula 1.
[0172] Type 1: All-solid-state battery with non-plated negative electrode
[0173] Figure 7 Schematic diagram of an all-solid battery including a non-plating type negative electrode according to an example embodiment. In the all-solid battery including a non-plating type negative electrode, during initial charging, the initial charge capacity of the negative electrode active material layer may be, for example, greater than 50%, 60% or more, 70% or more, 80% or more, 90% or more, or 100% or more relative to the initial charge capacity of the positive electrode active material layer.
[0174] An all-solid-state lithium battery can be prepared as follows.
[0175] First, a solid electrolyte layer can be prepared. The solid electrolyte layer may include a solid electrolyte. For example, the solid electrolyte layer can be prepared by mixing and drying a solid electrolyte containing a compound represented by Formula 1 and a binder, or can be prepared by pressing a solid electrolyte powder containing a compound represented by Formula 1 into a specific form. For example, the solid electrolyte layer can be prepared by mixing and drying a solid electrolyte containing a compound represented by Formula 1, a sulfide and / or oxide solid electrolyte, and a binder, or can be prepared by pressing a solid electrolyte powder containing a compound represented by Formula 1 and a sulfide and / or oxide solid electrolyte powder into a specific form. For example, the solid electrolyte layer can be prepared by mixing and drying a sulfide and / or oxide solid electrolyte and a binder, or can be prepared by pressing a sulfide and / or oxide electrolyte powder into a specific form.
[0176] For example, the solid electrolyte can be deposited using a film-forming method, thereby forming a solid electrolyte layer, where the film-forming method can be by blasting, aerosol deposition, cold spraying, sputtering, chemical vapor deposition, spraying, etc. Additionally, the solid electrolyte layer can be formed by pressing the solid electrolyte. Additionally, the solid electrolyte layer can be formed by mixing and pressing a solid electrolyte, a solvent, and a binder or carrier. In this case, the solvent or carrier can be added to enhance the strength of the solid electrolyte layer or prevent short-circuiting of the solid electrolyte.
[0177] The binder included in the solid electrolyte layer can be, for example, styrene-butadiene rubber (“SBR”), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polyvinyl alcohol, etc., but is not limited to the foregoing materials, and any binder available in the art can be used. The binder in the solid electrolyte layer can be the same as or different from the binder in the positive electrode layer and the negative electrode layer.
[0178] The oxide solid electrolyte can be, for example, one or more of the following: Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 < x < 2 and 0 ≤ y < 3), BaTiO 3 、Pb(Zr a Ti 1-a )O 3 (“PZT”, 0 ≤ a ≤ 1), Pb 1-x La x Zr 1-y Ti y O 3(“PLZT”) (0 ≤ x < 1 and 0 ≤ y < 1), Pb(Mg 1 / 3 Nb 2 / 3 )O 3 -PbTiO 3 (“PMN-PT”), HfO 2 、SrTiO 3 、SnO 2 、CeO 2 、Na 2 O、MgO、NiO、CaO、BaO、ZnO、ZrO 2 、Y 2 O 3 、Al 2 O 3 、TiO 2 、SiO 2 、Li 3 PO 4 、Li x Ti y (PO 4 ) 3 (0 < x < 2 and 0 < y < 3), Li x Al y Ti z (PO 4 ) 3 (0 < x < 2, 0 < y < 1, and 0 < z < 3), Li 1+x+y (Al a Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P 3-y O 12 (0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ a ≤ 1, and 0 ≤ b ≤ 1), Li x La y TiO 3 (0 < x < 2 and 0 < y < 3), Li 2 O、LiOH、Li 2 CO 3 、LiAlO 2 、Li 2 O-Al 2 O 3 -SiO 2 -P 2 O 5 -TiO 2 -GeO 2 、或Li 3+x La 3 M 2O 12 (where M is Te, Nb, or Zr, and x is an integer from 1 to 10). The solid electrolyte can be manufactured by a method such as a sintering method. The oxide solid electrolyte can be, for example, a garnet-type solid electrolyte as follows: Li 7 La 3 Zr 2 O 12 (“LLZO”), Li 3+x La 3 Zr 2-a M a O 12 (“M-doped LLZO”, where M is Ga, W, Nb, Ta, or Al, 0 < a < 2, and x is in the range of 1 to 10), or a combination thereof.
[0179] Examples of the sulfide solid electrolyte include lithium sulfide, silicon sulfide, phosphorus sulfide, boron sulfide, or a combination thereof. The sulfide solid electrolyte particles can include Li 2 S, P 2 S 5 SiS 2 GeS 2 B 2 S 3 or a combination thereof. The sulfide solid electrolyte particles can be Li 2 S or P 2 S 5 . It is known that the sulfide solid electrolyte particles have a higher lithium ion conductivity than other inorganic compounds. For example, the sulfide solid electrolyte can include Li 2 S and P 2 S 5 . If the sulfide solid electrolyte material constituting the solid electrolyte includes Li 2 S-P 2 S 5 , then the mixing molar ratio of Li 2 S to P 2 S 5 can be, for example, in the range of about 50:50 to about 90:10.
[0180] The sulfide solid electrolyte can also include an inorganic solid electrolyte prepared by: combining Li 3 PO 4 , a halogen, a halogen compound, Li 2+2x Zn 1-x GeO 4 (0 ≤ x ≤ 1) (“LISICON”), Li 3+y PO 4-x N x(0≤x≤1,0≤y≤1)(“LIPON”), Li 3.25 Ge 0.25 P 0.75 S 4 ("ThioLISICON"), Li 2 O-Al 2 O 3 -TiO 2 -P 2 O 5 ("LATP") etc. are added to Li 2 SP 2 S 5 、SiS 2 ,GeS 2 , B 2 S 3 , or a combination thereof.
[0181] Non-limiting examples of the sulfide solid electrolyte material include Li 2 SP 2 S 5 ;Li 2 SP 2 S 5 -LiX (X is a halogen element, such as Cl, Br, or I); Li 2 SP 2 S 5 -Li 2 O; Li 2 SP 2 S 5 -Li 2 O-LiI;Li 2 S-SiS 2 ;Li 2 S-SiS 2 -LiI; Li 2 S-SiS 2 -LiBr; Li 2 S-SiS 2 -LiCl; Li 2 S-SiS 2 -B 2 S 3 -LiI; Li 2 S-SiS 2 -P 2 S 5 -LiI; Li 2 SB 2 S 3 ;Li 2 SP 2 S 5 -Zm S n (where m and n are each positive numbers, and Z is Ge, Zn, or Ga); Li 2 S-GeS 2 ; Li 2 S-SiS 2 -Li 3 PO 4 ; or Li 2 S-SiS 2 -Li p MO q (where p and q are each positive numbers, and M is P, Si, Ge, B, Al, Ga, or In). In this regard, the sulfide solid electrolyte material can be prepared as follows: subjecting the starting materials of the sulfide solid electrolyte (e.g., Li 2 S, P 2 S 5 etc.) to treatments such as melt quenching, mechanical grinding, etc. Additionally, a calcination process can be carried out after the above treatments.
[0182] In addition, among the sulfide solid electrolyte materials described above, the sulfide solid electrolyte can be a material containing at least sulfur (S), phosphorus (P), and lithium (Li) as its constituent elements. For example, the sulfide solid electrolyte can be a material including Li 2 S-P 2 S 5 . If a material including Li 2 S-P 2 S 5 is used as the sulfide solid electrolyte material, then the mixing molar ratio of Li 2 S to P 2 S 5 can be, for example, in the range of about 50:50 to about 90:10.
[0183] The sulfide solid electrolyte can be a compound having a thiogermanate crystal structure. The compound having a thiogermanate crystal structure can include, for example, Li 7-x PS 6-x Cl x (0 < x < 2), Li 7-x PS 6-x Br x (0 < x < 2), or Li 7-x PS 6- x I x (0 < x < 2), one or more of these. For example, the sulfide solid electrolyte included in the solid electrolyte can be a thiogermanate-type compound, which includes Li 6 PS 5Cl, Li 6 PS 5 Br, or Li 6 PS 5 I. As used herein, argyrodite is a sulfide ore having the formula Ag. 8 G JZ 6 As used herein, the term "argyrodite compound" means that the compound is isostructural with argyrodite.
[0184] Next, the positive electrode can be prepared.
[0185] The positive electrode may be prepared by forming a positive electrode active material layer including a positive electrode active material on a positive electrode current collector. The positive electrode active material layer may be prepared by a gas phase method, a liquid phase process or a solid phase method. The gas phase method may include methods such as pulsed laser deposition (PLD), sputtering deposition, and chemical vapor deposition (CVD), but is not limited to the foregoing methods, and any method available in the art may be used. The liquid phase process or solid phase method may include methods such as sintering, sol-gel technology, doctor blade technology, screen printing, slurry casting, and powder pressing, but is not limited to the foregoing methods, and any method available in the art may be used.
[0186] The positive electrode active material layer may include a positive electrode active material. The positive electrode active material and the positive electrode current collector may be selected from the aforementioned materials used in lithium ion batteries.
[0187] The positive electrode active material layer may further include a binder, a conductive material, etc. The binder and the conductive material may be selected from the aforementioned materials used in lithium ion batteries.
[0188] The positive electrode active material layer may include the solid electrolyte according to the embodiment. A protective layer including the solid electrolyte according to the embodiment may be provided on the positive electrode active material layer.
[0189] Next, the negative electrode can be prepared.
[0190] The negative electrode may be prepared in the same manner as the positive electrode, except that a negative electrode active material is used instead of the positive electrode active material. The negative electrode may be prepared by forming a negative electrode active material layer including the negative electrode active material on a negative electrode current collector.
[0191] The negative electrode active material layer may include a negative electrode active material. The negative electrode active material may be selected from the aforementioned materials used in lithium ion batteries. The negative electrode active material layer may be, for example, lithium metal, a lithium metal alloy, or a combination thereof.
[0192] The negative electrode active material layer may further include a binder, a conductive material, etc. The binder and the conductive material may be selected from the aforementioned materials used in lithium ion batteries.
[0193] The negative electrode active material layer may include the solid electrolyte according to an embodiment. A protective layer including the solid electrolyte according to an embodiment may be provided on the negative electrode active material layer.
[0194] refer to Figure 7 , the all-solid battery 40 may include a solid electrolyte layer 30, a positive electrode 10 disposed on one side of the solid electrolyte layer 30, and a negative electrode 20 disposed on the other side of the solid electrolyte layer 30. The positive electrode 10 may include a positive electrode active material layer 12 in contact with the solid electrolyte layer 30, and a positive electrode collector 11 in contact with the positive electrode active material layer 12. The negative electrode 20 may include a negative electrode active material layer 22 in contact with the solid electrolyte layer 30, and a negative electrode collector 21 in contact with the negative electrode active material layer 22. For the all-solid battery 40, for example, the positive electrode active material layer 12 and the negative electrode active material layer 22 may be formed on each side of the solid electrolyte layer 30, and the positive electrode collector 11 and the negative electrode collector 21 may be formed on the positive electrode active material layer 12 and the negative electrode active material layer 22, respectively, to thereby complete the preparation of the all-solid battery 40. Alternatively, the negative electrode active material layer 22 , the solid electrolyte layer 30 , the positive electrode active material layer 12 , and the positive electrode collector 11 may be sequentially stacked on the negative electrode collector 21 to thereby complete the preparation of the all-solid battery 40 .
[0195] Type 2: All-solid-state battery with plated negative electrode
[0196] Figure 8 and 9 Schematic diagram of an all-solid battery including a plated negative electrode according to an example embodiment. In an all-solid battery including a plated negative electrode, during initial charging, the initial charge capacity of the negative electrode active material layer may be, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 5% or less, or 1% or less relative to the initial charge capacity of the positive electrode active material layer. The all-solid battery 40 may include, for example, a positive electrode 10 including a positive electrode active material layer 12 disposed on a positive electrode collector 11; a negative electrode 20 including a negative electrode active material layer 12 disposed on a negative electrode collector 21; and an electrolyte layer 30 disposed between the positive electrode 10 and the negative electrode 20, wherein the positive electrode active material layer 12 and / or the electrolyte layer 30 may include a solid electrolyte.
[0197] An all-solid battery according to another embodiment may be prepared as follows.
[0198] The positive electrode and the solid electrolyte layer may be prepared according to the same process as in the all-solid secondary battery provided with the non-plating type negative electrode described above.
[0199] Next, the negative electrode can be prepared.
[0200] refer to Figure 8 and 9 The negative electrode 20 may include a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on the negative electrode current collector 21 , wherein the negative electrode active material layer 22 may include, for example, a negative electrode active material and a binder.
[0201] The negative active material included in the negative active material layer 22 may have, for example, a particle form. The negative active material having a particle form may have, for example, an average particle diameter of 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, or 900 nm or less. The average particle diameter of the negative active material having a particle form may be, for example, from about 10 nanometers (nm) to about 4 μm, from about 10 nm to about 3 μm, from about 10 nm to about 2 μm, from about 10 nm to about 1 μm, or from about 10 nm to about 900 nm. Using a negative active material having an average particle diameter within the above range, reversible absorption and / or desorption of lithium during charge / discharge may be promoted. The average particle diameter of the negative active material may be, for example, a median particle diameter (D50) as measured by a laser-type particle size distribution analyzer.
[0202] The negative electrode active material included in the negative electrode active material layer 22 may include, for example, at least one of a negative electrode active material containing carbon or a metal or metalloid negative electrode active material.
[0203] The negative electrode active material containing carbon may be, for example, amorphous carbon. Examples of the amorphous carbon include carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), graphene, etc.; however, the negative electrode active material containing carbon is not limited to the aforementioned examples, and may be any material classified as amorphous carbon in the art. Amorphous carbon is carbon that does not have a crystalline structure or has a very low degree of crystallinity, and therefore, can be distinguished from crystalline carbon or graphite carbon.
[0204] The metal or metalloid negative electrode active material may include one or more of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), or zinc (Zn), but is not limited thereto, and may be any material in the art used as a metal negative electrode active material or a metalloid negative electrode active material that forms an alloy or compound with lithium. For example, nickel (Ni) does not form an alloy with lithium and is therefore not considered a metal negative electrode active material.
[0205] The negative electrode active material layer 22 may include a single negative electrode active material among the aforementioned negative electrode active materials or a mixture of multiple different types of negative electrode active materials. For example, the negative electrode active material layer 22 may include amorphous carbon alone, or may include one or more of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), or zinc (Zn). Alternatively, the negative electrode active material layer 22 may include a mixture of amorphous carbon and one or more of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), or zinc (Zn). The mixing ratio of amorphous carbon to the metal described herein, such as gold (Au), in such a mixture may be, by weight, for example, about 10:1 to about 1:2, about 5:1 to about 1:1, or about 4:1 to about 2:1, but is not necessarily limited thereto and may be selected according to the desired characteristics of the all-solid battery 40. Since the negative electrode active material has the aforementioned composition, the cycle performance of the all-solid battery 40 may be further improved.
[0206] The negative electrode active material included in the negative electrode active material layer 22 may include, for example, a mixture of first particles and second particles, the first particles being composed of amorphous carbon, and the second particles being composed of metal or metalloid. Examples of the metal or metalloid include gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), etc. Alternatively, the metalloid may be a semiconductor. The amount of the second particle may be about 8 wt % to about 60 wt %, about 10 wt % to about 50 wt %, about 15 wt % to about 40 wt %, or about 20 wt % to about 30 wt %, relative to the total weight of the mixture. If the amount of the second particle is within the aforementioned range, for example, the cycle performance of the all-solid battery 40 may be further improved.
[0207] The binder included in the negative electrode active material layer 22 may be, for example, styrene butadiene rubber ("SBR"), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc. However, the binder is not limited to the aforementioned examples, and may be any material that can be used as a binder in the art. The binder may be composed of a single type of binder, or a plurality of binders of different types.
[0208] Since the negative electrode active material layer 22 includes a binder, the negative electrode active material layer 22 can be stabilized on the negative electrode collector 21. In addition, crack formation in the negative electrode active material layer 22 can be suppressed despite the volume change and / or displacement of the negative electrode active material layer 22 during the charging and discharging process. For example, if the negative electrode active material layer 22 does not contain any binder, the negative electrode active material layer 22 can be easily delaminated from the negative electrode collector 21. At the area where the negative electrode collector 21 is exposed due to the delamination of the negative electrode active material layer 22 from the negative electrode collector 21, the negative electrode collector 21 and the solid electrolyte layer 30 may contact each other, thereby increasing the possibility of short circuit occurrence. For example, the negative electrode active material layer 22 can be prepared by applying and drying a slurry in which a material forming the negative electrode active material layer 22 is dispersed on the negative electrode collector 21. By including a binder in the negative electrode active material layer 22, stable dispersion of the negative electrode active material in the slurry can be achieved. For example, if the slurry is applied to the negative electrode collector 21 by a screen printing method, it may be possible to prevent the screen from being clogged (eg, clogged by aggregates of the negative electrode active material).
[0209] The negative electrode active material layer 22 may further include other additives used in all-solid batteries, such as fillers, coating agents, dispersants, ion conduction aids, and the like.
[0210] For example, the negative electrode active material layer 22 may have a thickness of 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less relative to the thickness of the positive electrode active material layer 12. For example, the negative electrode active material layer 22 may have a thickness of about 1 μm to about 20 μm, about 2 μm to about 10 μm, or about 3 μm to about 7 μm. If the negative electrode active material layer 22 is too thin, the negative electrode active material layer 22 may be disintegrated by lithium dendrites formed between the negative electrode active material layer 22 and the negative electrode current collector 21, making it difficult to improve the cycle performance of the all-solid battery 40. If the thickness of the negative electrode active material layer 22 is excessively increased, the energy density of the all-solid battery 40 may be reduced, while the internal resistance of the all-solid battery 40 through the negative electrode active material layer 22 increases, making it difficult to improve the cycle performance of the all-solid battery 40.
[0211] If the thickness of the negative active material layer 22 is reduced, for example, the charge capacity of the negative active material layer 22 is also reduced. For example, the charge capacity of the negative active material layer 22 may be 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 5% or less, and 2% or less, or 1% or less relative to the charge capacity of the positive active material layer 12. The charge capacity of the negative active material layer 22 may be, for example, about 0.1% to about 50%, about 0.1% to about 40%, about 0.1% to about 30%, about 0.1% to about 20%, about 0.1% to about 10%, about 0.1% to about 5%, or about 0.1% to about 2% relative to the charge capacity of the positive active material layer 12. If the initial charge capacity of the negative electrode active material layer 22 is too small, the thickness of the negative electrode active material layer 22 becomes extremely small, and therefore, the negative electrode active material layer 22 may be collapsed by lithium dendrites formed between the negative electrode active material layer 22 and the negative electrode current collector 21 during repeated charge / discharge processes, making it difficult to improve the cycle performance of the all-solid battery 40. If the charge capacity of the negative electrode active material layer 22 is excessively increased, the energy density of the all-solid battery 40 may be reduced, while the internal resistance of the all-solid battery 40 through the negative electrode active material layer 22 is increased, making it difficult to improve the cycle performance of the all-solid battery 40.
[0212] The charge capacity of the positive electrode active material layer 12 can be obtained by multiplying the charge capacity (milliampere / gram, mAh / g) of the positive electrode active material by the mass of the positive electrode active material in the positive electrode active material layer 12. If multiple types of positive electrode active materials are used, the product of the charge capacity×mass can be calculated for each positive electrode active material, and the sum of these products can be defined as the initial charge capacity of the positive electrode active material layer 12. The charge capacity of the negative electrode active material layer 22 can also be calculated in the same manner. For example, the charge capacity of the negative electrode active material layer 22 can be obtained by multiplying the charge capacity (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the negative electrode active material layer 22. If multiple types of negative electrode active materials are used, the product of the charge capacity×mass can be calculated for each negative electrode active material, and the sum of these products can be defined as the charge capacity of the negative electrode active material layer 22. For example, the charge capacity of each of the positive electrode active material and the negative electrode active material can be the capacity evaluated using an all-solid half-cell using lithium metal as a counter electrode. By using the charge capacity measurement of the all-solid half-cell, the charge capacity of each of the positive active material layer 12 and the negative active material layer 22 can be directly measured. The charge specific capacity can be obtained by dividing the measured charge capacity by the mass of the corresponding active material. In other embodiments, the charge capacity of each of the positive active material layer 12 and the negative active material layer 22 can be the initial charge capacity measured during the first cycle charge.
[0213] refer to Fig. 9 , the all-solid battery 40a may further include, for example, a metal layer 23 disposed between the negative electrode current collector 21 and the negative electrode active material layer 22. The metal layer 23 may be a metal foil or a plated metal layer. The metal layer 23 may include lithium or a lithium alloy. Therefore, the metal layer 23 may serve as, for example, a lithium reservoir. The lithium alloy may include, for example, a Li-Al alloy, a Li-Sn alloy, a Li-In alloy, a Li-Ag alloy, a Li-Au alloy, a Li-Zn alloy, a Li-Ge alloy, a Li-Si alloy, etc., but is not limited thereto, and may be any material that can be used as a lithium alloy in the art. The metal layer 23 may be composed of lithium or one of such alloys, or may be composed of a plurality of types of alloys.
[0214] The metal layer 23 is not limited to any particular thickness, but may have, for example, a thickness of about 1 µm to about 200 µm, about 1 µm to about 100 µm, about 1 µm to about 70 µm, about 1 µm to about 50 µm, about 1 µm to about 30 µm, or about 1 µm to about 20 µm. If the metal layer 23 is too thin, the metal layer 23 may not fully function as a lithium reservoir. If the metal layer 23 is too thick, the all-solid battery 40 may have increased mass and volume and show significantly deteriorated cycle performance. The metal layer 23 may be, for example, a metal foil having a thickness within the aforementioned range.
[0215] In the all-solid battery 40a, the metal layer 23 may be disposed between the negative electrode current collector 21 and the negative electrode active material layer 22, for example, before the assembly of the all-solid battery 40a, or the metal layer 23 may be plated between the negative electrode current collector 21 and the negative electrode active material layer 22 after the assembly of the all-solid battery 40a. In the case where the metal layer 23 is disposed between the negative electrode current collector 21 and the negative electrode active material layer 22 before the assembly of the all-solid battery 40a, the metal layer 23 may act as a lithium reservoir due to being a metal layer containing lithium. For example, before the assembly of the all-solid battery 40a, a lithium foil may be disposed between the negative electrode current collector 21 and the negative electrode active material layer 22. As a result, the cycle performance of the all-solid battery 40a including the metal layer 23 may be further improved. In the case where the metal layer 23 will be plated by charging after the assembly of the all-solid battery 40a, since the metal layer 23 is not present in the all-solid battery 40a at the time of its assembly, the energy density of the all-solid battery 40a may be increased. For example, if the all-solid battery 40a is charged, the charging may be performed to exceed the charge capacity of the negative electrode active material layer 22. The negative electrode active material layer 22 may then be overcharged. At the start of charging, lithium may be absorbed into the negative electrode active material layer 22. The negative electrode active material included in the negative electrode active material layer 22 may form an alloy or compound with lithium ions migrated from the positive electrode 10. Charging to exceed the capacity of the negative electrode active material layer 22 may result in, for example, lithium plating on the back side of the negative electrode active material layer 22, for example, between the negative electrode current collector 21 and the negative electrode active material layer 22, and the plated lithium may then form a metal layer corresponding to the metal layer 23. The metal layer 23 may be a metal layer mainly composed of lithium (ie, metallic lithium). This result may be obtained by the fact that the negative electrode active material included in the negative electrode active material layer 22 is formed of a material that forms an alloy or compound with lithium. During discharge, lithium in the metal layer, for example, the negative electrode active material layer 22 and the metal layer 23 may be ionized and migrate toward the positive electrode 10. Therefore, lithium can be used as the negative electrode active material in the all-solid battery 40a. In addition, since the negative electrode active material layer 22 covers the metal layer 23, the negative electrode active material layer 22 can play the role of a protective layer for the metal layer, such as the metal layer 23, while suppressing the growth and plating of lithium dendrites. Therefore, the short circuit and capacity decay of the all-solid battery 40a can be suppressed, and therefore, the cycle performance of the all-solid battery 40a can be improved. In addition, in the case where the metal layer 23 is placed by charging after the assembly of the all-solid battery 40a, the negative electrode current collector 21, the negative electrode active material layer 22, and the area therebetween may be, for example, a Li-free area that does not include lithium (Li) when the all-solid battery 40a is in an initial state or a state after discharge.
[0216] The negative electrode current collector 21 may be formed of a material that does not react with lithium, for example, does not form an alloy or compound with lithium. Examples of materials forming the negative electrode current collector 21 include copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), etc. However, the material forming the negative electrode current collector 21 is not necessarily limited to the aforementioned materials, but may be any material that can be used as an electrode current collector in the art. The negative electrode current collector 21 may be formed of one type of the aforementioned metals, an alloy of two or more types of metals thereof, or a covering material. The negative electrode current collector 21 may be, for example, a plate type or a foil type.
[0217] The all-solid battery 40, 40a may further include, for example, a thin film (not shown) containing an element capable of forming an alloy with lithium ions on the negative electrode current collector 21. The thin film may be disposed between the negative electrode current collector 21 and the negative electrode active material layer 22. The thin film may include, for example, an element capable of forming an alloy with lithium. Examples of the element capable of forming an alloy with lithium include gold (Au), silver (Ag), zinc (Zn), tin (Sn), indium (In), silicon (Si), aluminum (Al), bismuth (Bi), etc., but are not necessarily limited thereto, and any element capable of forming an alloy with lithium in the art may be used. The thin film may be composed of one of the aforementioned metals or may be composed of an alloy of multiple metals. With the thin film disposed on the negative electrode current collector 21, the shape of the metal layer 23 plated between the thin film and the negative electrode active material layer 22 may be further flattened, and the cycle performance of the all-solid battery 40a may be further improved.
[0218] For example, the film may have a thickness of about 1 nm to about 800 nm, about 10 nm to about 700 nm, about 50 nm to about 600 nm, or about 100 nm to about 500 nm. If the thickness of the film is less than 1 nm, it may be difficult to achieve the function attributable to the film. If the film is too thick, the film may absorb lithium itself, reducing the amount of lithium plated at the negative electrode, which may result in a reduction in the energy density of the all-solid battery and a deterioration in the cycle performance of the all-solid battery 40, 40a. The film may be placed on the negative electrode current collector 21 by a vacuum deposition method, a sputtering method, a plating method, etc., but is not limited to the aforementioned method and may be any method available in the art capable of forming the film.
[0219] Multilayer Ceramic (MLC) Battery
[0220] The MLC battery may include, for example, a plurality of positive electrode layers; a plurality of negative electrode layers alternately disposed between the plurality of positive electrode layers; and a solid electrolyte layer alternately disposed between the plurality of positive electrode layers and the plurality of negative electrode layers. The solid electrolyte included in the MLC battery may be, for example, an oxide solid electrolyte. For example, the solid electrolyte may include a solid electrolyte containing a compound represented by Formula 1.
[0221] The MLC battery may be, for example, a sintered product of a stacked structure in which a positive electrode active material precursor, a negative electrode active material precursor, and a solid electrolyte precursor are sequentially stacked, or may be a sintered product of a stacked structure in which a positive electrode active material, a negative electrode active material, and a solid electrolyte are sequentially stacked. The MLC battery may be provided with, for example, a stacked structure in which a plurality of unit cells are stacked, wherein a positive electrode active material layer faces a negative electrode active material layer and vice versa, and each unit cell includes: a positive electrode layer including a positive electrode active material layer; a solid electrolyte layer; and a negative electrode layer including a negative electrode active material layer, which are sequentially and continuously arranged. For example, the MLC battery may further include a positive electrode current collector and / or a negative electrode current collector. If the MLC battery includes a positive electrode current collector, a positive electrode active material layer may be provided on both sides of the positive electrode current collector. If the MLC battery includes a negative electrode current collector, a negative electrode active material layer may be provided on both sides of the negative electrode current collector. Since the MLC battery further includes a positive current collector and / or a negative current collector, the high rate performance of the battery can be further improved. In the MLC battery, the unit cells can be stacked together by providing a current collector layer on either or both of the topmost layer and the bottommost layer of the stacked structure, or introducing a metal layer into the stacked structure. The MLC battery or thin film battery can be a small or ultra-small battery, which can be used, for example, as a power source for applications in the Internet of Things (IoT) or a power source for wearable devices. The MLC battery or thin film battery can also be used in medium to large batteries in electric vehicles (EVs), energy storage systems (ESSs), etc.
[0222] The negative electrode included in the MLC battery may include, for example, one or more of the following negative electrode active materials: lithium metal phosphate, lithium metal oxide, metal oxide, or a negative electrode active material containing carbon.
[0223] The negative electrode active material containing carbon includes crystalline carbon, amorphous carbon, porous carbon, or a combination thereof.
[0224] Examples of crystalline carbon include natural graphite or artificial graphite. Amorphous carbon is, for example, carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), graphene, soft carbon or hard carbon, mesophase pitch carbonization product, calcined coke, etc. The negative electrode active material may be, for example, a compound selected from the following: Li 4 / 3 Ti 5 / 3 O 4 、LiTiO 2 、LiM1 s M2 t O u (M1 and M2 are each a transition metal, and s, t, and u are each any positive number), TiOx (0 < x ≤ 3), or Li x V 2 (PO 4 ) 3 (0 < x ≤ 5). The negative electrode active material can be, in particular, Li 4 / 3 Ti 5 / 3 O 4 , LiTiO 2 etc.
[0225] The positive electrode included in the MLC battery may include a positive electrode active material. The positive electrode active material can be selected from the positive electrode active materials used in the aforementioned lithium ion batteries. The positive electrode active material can include, for example, one or more of lithium metal phosphates or lithium metal oxides. Examples of the positive electrode active material include lithium cobalt oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, or a combination thereof.
[0226] The current collector layer can function as a positive electrode current collector and / or a negative electrode current collector. The current collector layer can be formed, for example, from any metal of Ni, Cu, Ag, Pd, Au, or Pt. The current collector layer can be made of an alloy containing any one of Ni, Cu, Ag, Pd, Au, or Pt, for example. The alloy can be, for example, an alloy of two or more of Ni, Cu, Ag, Pd, Au, or Pt. The alloy can be, for example, an Ag / Pd alloy. Such metals and alloys can be of a single type or a mixture of two or more types. The current collector layer as the positive electrode current collector and the current collector layer as the negative electrode current collector can use the same material or different materials from each other. Due to the alloy or mixed powder containing Ag and Pd, by adjusting its mixing ratio, its melting point can be adjusted to any melting point between the melting point of silver (962 °C) and the melting point of palladium (1,550 °C), so the melting point can be adjusted to the batch sintering temperature. In addition, the alloy or mixed powder containing Ag and Pd, due to its high electron conductivity, can suppress the increase in battery internal resistance.
[0227] The solid electrolyte can be, for example, an oxide solid electrolyte. The oxide solid electrolyte can be selected from the materials used in the aforementioned all-solid-state batteries. For example, the solid electrolyte can be a lithium compound selected from the following: Li 3.25 Al 0.25 SiO 4 , Li 3 PO 4 , and LiP x Si y O z (in this formula, x, y, and z are each any positive number). The solid electrolyte can be, for example, Li 3.5 P 0.5Si 0.5 O 4 .
[0228] Fig.10 FIG. 1 is a schematic cross-sectional view of an MLC battery 150 according to an embodiment. Fig.10 , the positive electrode active material layer 112 may be disposed on both sides of the positive electrode collector 111 to form the positive electrode 110. The negative electrode active material layer 122 may be stacked on both sides of the negative electrode collector 121 to form the negative electrode 120. The solid electrolyte 130 may be disposed between the positive electrode 110 and the negative electrode 120. The external electrode 140 may be formed on both ends of the battery body. The external electrode 140 may be connected to the positive electrode 110 and the negative electrode 120, each of which has a tip portion exposed to the outside of the battery body and serves as an external terminal that electrically connects the positive electrode 110 and the negative electrode 120 to an external element. One of a pair of external electrodes 140 may have one end connected to the positive electrode 110 exposed to the outside of the battery body, and the other of a pair of external electrodes 140 may have the other end connected to the negative electrode 120 exposed to the outside of the battery body. The MLC battery 150 may be prepared by sequentially stacking the oxide electrode and the solid electrolyte and then simultaneously heat-treating.
[0229] Fig.11 and 12 Schematically shows the cross-sectional structure of an MLC battery according to another embodiment. Fig.11 As shown in FIG. 1 , in the MLC battery 710, the unit cell 1 and the unit cell 2 may be stacked through the internal current collector layer 74. The unit cell 1 and the unit cell 2 may each be composed of a positive electrode layer 71, a solid electrolyte layer 73, and a negative electrode layer 72 stacked sequentially. The unit cell 1, the unit cell 2, and the internal current collector layer 74 may be stacked so that the negative electrode layer 72 of the unit cell 2 is adjacent to one side of the internal current collector layer 74 ( Fig.11 The negative electrode layer 72 of the unit cell 1 is adjacent to the other side of the internal current collector layer 74 ( Fig.11 The bottom surface in the Fig.111 and 2 are shown as being arranged in contact with the negative electrode layer 72 of each of the unit cell 1 and the unit cell 2, but the internal current collector layer 74 may also be arranged in contact with the positive electrode layer 71 of each of the unit cell 1 and the unit cell 2. The internal current collector layer 74 may include an electronic conductive material. The internal current collector layer 74 may further include an ion conductive material. Further including an ion conductive material can improve voltage stability characteristics. Since in the MLC battery 710, both sides of the internal current collector layer 74 have the same polarity, a single-pole type MLC battery 710 can be obtained, which has a plurality of unit cells connected in parallel to each other by the internal current collector layer 74 inserted therein. As a result, a high-capacity MLC battery 710 can be obtained. Since in the MLC battery 710, the internal current collector layer 74 inserted between the unit cell 1 and the unit cell 2 contains an electronic conductive material, parallel electrical connection between two adjacent unit cells can become possible, and at the same time, ion conductive connection between the positive electrode layer 71 or the negative electrode layer 72 in two adjacent unit cells can become possible. Since the potential of the adjacent negative electrode layer 71 or positive electrode layer 72 can be averaged by the internal current collector layer 74, a stable output voltage can be obtained. In addition, an external current collecting member such as a tab can be omitted, and parallel electrical connection between unit cells constituting the MLC battery 710 can become possible. As a result, an MLC battery 710 with excellent space efficiency and cost effectiveness can be obtained. Reference Fig.12 , the stacked structure may contain a positive electrode layer 81, a negative electrode layer 82, a solid electrolyte layer 83, and an internal current collector layer 84. The stacked structure may be stacked and heat-compressed to form an MLC battery stack 810. The positive electrode layer 81 may be composed of a single positive electrode layer sheet, and the negative electrode layer 82 may be composed of two negative electrode layer sheets.
[0230] Method for preparing solid electrolyte
[0231] A method for preparing a solid electrolyte according to an embodiment may include: mixing a metal precursor including at least one of iron (Fe), chromium (Cr), lanthanum (La), or thallium (Tl), a lithium precursor, a silicon precursor, a boron precursor, and a solvent to obtain a mixture; performing a first heat treatment on the mixture to provide a first heat-treated mixture; performing a second heat treatment on the first heat-treated mixture to provide a product; and quenching the product to provide the solid electrolyte.
[0232] In obtaining the mixture, the corresponding amounts of the metal precursor, lithium precursor, silicon precursor, and boron precursor can be stoichiometrically controlled to produce a desired oxide composition. The metal precursor, lithium precursor, silicon precursor, boron precursor, and solvent are mixed to provide a mixture which can be carried out by stirring (mechanical stirring, etc.).
[0233] The metal precursor containing at least one of iron (Fe), chromium (Cr), lanthanum (La), or thallium (Tl) can be prepared using, for example, Fe 2 O 3 Cr 2 O 3 ,La 2 O 2 , or Tl 2 O 3 .
[0234] The lithium precursor can be Li 2 O. Li 2 CO 3 、LiCl、LiNO 3 , or Li(OH) or more. In addition, the silicon precursor can be tetraethyl orthosilicate, SiO 2 , or a combination thereof, and the boron precursor may be H 3 BO 3 or B 2 O 3 At least one of the following. The raw material containing lithium and boron may include Li 3 BO 3 , and the raw materials containing lithium and silicon may include Li 4 SiO 4 .
[0235] The solvent used may be deionized water, an organic solvent, or a combination thereof.
[0236] Using an organic solvent as a solvent can prevent dissolution of the lithium (Li) component and can obtain a mixture of uniform composition.
[0237] The organic solvent may be one or more of the following: an alcohol-based solvent, a ketone-based solvent, an ester-based solvent, a glycol ether-based solvent, a hydrocarbon-based solvent, an ether solvent, a glycol-based solvent, or an amine-based solvent. For example, the organic solvent may be at least one of the following: an alcohol-based solvent such as methanol, ethanol, butanol, hexanol, benzyl alcohol, or isopropanol; a ketone-based solvent such as acetone, methyl ethyl ketone, methyl isobutyl ketone, or cyclohexanone; an ester-based solvent such as methyl acetate, ethyl acetate, or butyl acetate; a glycol ether-based solvent such as propylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, 3-methoxy-3-methyl-1-butanol, or diethylene glycol monobutyl ether; a hydrocarbon-based solvent The invention can be used as a solvent such as benzene, toluene, xylene, cyclohexane, methylcyclohexane, ethylcyclohexane, mineral oil, normal paraffin, or isoparaffin; an ether solvent such as 1,3-dioxolane, 1,4-dioxane, or tetrahydrofuran; a glycol-based solvent such as ethylene glycol, diethylene glycol, propylene glycol, or polyethylene glycol; or an amine-based solvent such as monoethanolamine, diethylamine, triethanolamine, N-methyl-2-pyrrolidone, 2-amino-2-methyl-1-propanol, or N,N-dimethylformamide.
[0238] Through the first heat treatment, the second heat treatment and the quenching process, a vitrified oxide can be obtained.
[0239] The second heat treatment may be performed at a temperature greater than the first heat treatment, the first heat treatment may be a preheat treatment and performed at a temperature of about 200°C to about 450°C, the second heat treatment may be a heat treatment process for forming glass, and the second heat treatment may be performed at a temperature of about 700°C to about 1,000°C.
[0240] During the quenching, the cooling rate may be about 10 2 Kelvin / second (K / s) to about 10 5 If the quenching is performed at the aforementioned cooling rate, a solid electrolyte having a glass oxide having desired properties can be prepared.
[0241] In the present disclosure, if each precursor is in a molten state, the quenching can be performed by any one of water atomization, gas atomization, centrifugal atomization, twin-roll spinning, or melt spinning. If the raw material is in a gaseous state, the quenching can be performed by one or more cooling media in the quenching gas, the inner wall of the reactor, or the capture tube.
[0242] Prior to the first heat treatment, drying the mixture may be performed to provide a dried mixture, wherein the drying may be performed at a temperature of about 50° C. to about 90° C. During the drying process, the solvent may be removed.
[0243] The solid electrolyte according to the embodiment can provide a solid electrolyte that uses an oxide in an amorphous state and, therefore, exhibits excellent mechanical properties and has excellent electrochemical stability and chemical stability even without an additional sintering process for densification, while having high ion conductivity. Such a solid electrolyte can be used as a solid electrolyte component (component) for a solid secondary battery.
[0244] Hereinafter, the present disclosure will be described in more detail with respect to Examples and Comparative Examples, but it is not limited to the Examples disclosed below.
[0245] Preparation of Li-B-Si-MO oxide and solid electrolyte
[0246] Example 1: Li-B-Si-Fe-O oxide and solid electrolyte
[0247] The oxide-forming composition was prepared by mixing the following components: 2 M tetraethylorthosilicate (TEOS) solution in ethanol; 1 M boric acid solution in ethanol; 3 M LiNO in deionized water. 3 solution; 4M citric acid solution in deionized water; and Fe 2 O 3 The composition of TEOS, boric acid, LiNO 3 , and Fe 2 O 3 The corresponding amounts of 4 M citric acid solution were used to provide metal oxides having the compositions shown in Table 1. Here, the amount of the 4 M citric acid solution was 1 ml based on 100 ml of the TEOS solution.
[0248] The oxide-forming composition was dried at 70°C in air for 12 hours, heated to 350°C at a heating rate of 2 degrees Celsius / minute (°C / minute), and then subjected to a first heat treatment (first heat treatment) at 350°C for 3 hours. The brown powder thus produced was crushed and flaked to prepare a disc, and the disc was placed in a platinum (Pt) cup made of a 0.1 millimeter (mm) thick Pt foil (8 mm × 8 mm square) having a depth of 0.4 mm and a diameter of 6 mm. The Pt cup containing the disc was placed on a single alumina plate, heated to 900°C at a heating rate of 5°C / minute, and then subjected to a second heat treatment (second heat treatment) at 900°C for 30 minutes.
[0249] Subsequently, the Pt cup containing the disc disposed on the alumina plate was transferred to a stainless steel plate to quench the sample to room temperature (25°C) within 5 seconds and thereby prepare a solid electrolyte containing Li-B-Si-Fe-O oxide having a thickness of about 0.3 mm and a weight of about 25 milligrams (mg).
[0250] Example 2: Li-B-Si-Cr-O oxide and solid electrolyte
[0251] Li—B—Si—Cr—O oxide and solid electrolyte were prepared in the same manner as in Example 1, except that when forming the oxide composition, Cr was used. 2 O 3 Instead of Fe 2 O 3 .
[0252] Example 3: Li-B-Si-La-O oxide and solid electrolyte
[0253] Li—B—Si—La—O oxide and solid electrolyte were prepared by the same procedure as in Example 1, except that when forming the oxide composition, La was used. 2 O 3 Instead of Fe 2 O 3 .
[0254] Example 4: Li-B-Si-Tl-O oxide and solid electrolyte
[0255] Li—B—Si—Tl—O oxide and solid electrolyte were prepared according to the same procedure as in Example 1, except that when forming the oxide composition, Tl was used. 2 O 3 Instead of Fe 2 O 3 .
[0256] Example 5: Li-B-Si-Cr-O oxide and solid electrolyte
[0257] Li-B-Si-Cr-O oxide and solid electrolyte were prepared in the same manner as in Example 1, except that when preparing the oxide, Cr 2 O 3 Instead of Fe 2 O 3 , and the amount of each precursor is controlled to provide a metal oxide having a composition as shown in Table 1.
[0258] Examples 6 to 7: Li-B-Si-Fe-O oxide and solid electrolyte
[0259] Li-B-Si-Fe-O oxide and solid electrolyte were prepared in the same manner as in Example 1, except that the TEOS, boric acid, LiNO and 3 , and Fe 2 O 3 The corresponding amounts are used to provide metal oxides having the compositions shown in Table 2.
[0260] Comparative Example 1: Li-B-Si-O oxide and solid electrolyte
[0261] Li—B—Si—O oxide and solid electrolyte were prepared in the same manner as in Example 1, except that Fe was omitted when preparing the oxide-forming composition. 2 O 3 , the amount of each precursor is controlled to provide a metal oxide having a composition as shown in Table 1.
[0262] Comparative Example 2: Li-B-Si-O oxide and solid electrolyte
[0263] Li—B—Si—O oxide and solid electrolyte were prepared in the same manner as in Example 1, except that Fe was omitted when preparing the oxide-forming composition. 2 O 3 , the amount of each precursor is controlled to provide a metal oxide having a composition as shown in Table 1.
[0264] Comparative Example 3: Li-B-Si-La-O oxide and solid electrolyte
[0265] Li—B—Si—La—O oxide and solid electrolyte were prepared in the same manner as in Example 1, except that when preparing the oxide-forming composition, La 2 O 3 Instead of Fe 2 O 3 , and the amount of each precursor is controlled to provide a metal oxide having a composition as shown in Table 1.
[0266] Table 1
[0267]
[0268] Table 2
[0269]
[0270] Preparation of all-solid-state secondary batteries
[0271] Example 8
[0272] Prepare 500 µm thick LLZO (Li7 La 3 Zr 2 O 12 ) disc as a solid electrolyte layer.
[0273] Separately, the first negative electrode active material layer slurry was bar-coated on a stainless steel (SUS) foil and dried at room temperature (25° C.) for 1 hour to thereby form a first negative electrode active material layer (AgC layer) (thickness: about 7 μm).
[0274] The first negative electrode active material layer slurry is prepared according to the following process.
[0275] As negative electrode active materials, carbon black (CB) having a primary particle diameter of about 38 nm and silver (Ag) particles having an average particle diameter of about 100 nm were prepared.
[0276] Carbon black ("CB", 3 grams) and silver particles (1 gram) were introduced into a container, and a PVA-PAA binder solution (2.692 grams, SUMITOMO SEIKA CHEMICALS CO., LTD, AG binder) mixed with distilled water (7 grams) was introduced into the container. The resulting mixture was stirred at 1,000 revolutions per minute (rpm) for 30 minutes to thereby form a first slurry. Zirconia balls (4 grams) and distilled water (20 grams) were introduced into the first slurry, followed by a second stirring at 1,000 rpm for 30 minutes to thereby prepare a second slurry. Distilled water (20 grams) was introduced into the second slurry, followed by a third stirring at 1,000 rpm for 30 minutes to thereby prepare a third slurry.
[0277] Meanwhile, the LLZO film was subjected to an acid treatment to manufacture an LLZO film having pores. For the acid treatment, a 1 M hydrochloric acid aqueous solution was used as an acid solution, and the LLZO film was immersed for 1 second and then washed with ethanol.
[0278] When the first negative electrode active material layer (AgC layer) is placed on the LLZO film, the SUS foil is removed. Then, a lithium metal foil (thickness: 20 μm) and a copper foil as a negative electrode current collector are stacked on the first negative electrode active material layer. Cold isostatic pressing (CIP, 250 MPa at 25°C) is applied to the resulting structure to thereby manufacture a solid electrolyte layer / first negative electrode active material layer / lithium metal / copper thin film stack.
[0279] Preparation of LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ("NCM") as the positive electrode active material, and the solid electrolyte Li 0.625 B0.321 Si 0.044 Fe 0.010 O 0.897 As a solid electrolyte. In addition, polytetrafluoroethylene (manufactured by Du Pont, TEFLON® binder) was prepared as a binder. In addition, carbon nanofibers ("CNF") were prepared as a conductive aid. Next, these positive electrode materials were mixed in a weight ratio of 80:20:2:1 of positive electrode active material: solid electrolyte: conductive aid: binder. The mixture was stretched into a sheet form to prepare a positive electrode active material sheet having a thickness of 30 μm. Then, the positive electrode active material sheet was compressed on a positive electrode current collector made of 18 μm thick aluminum foil to thereby prepare a positive electrode layer.
[0280] The positive electrode active material layer of the positive electrode layer thus prepared was immersed in a liquid containing N-propyl-N-methyl-pyrrolidone (bis(fluorosulfonyl)imide) dissolved in an ionic fluid. ) in an electrolyte of 2.0 M LiFSI.
[0281] The positive electrode layer is placed in a SUS cap so that the positive electrode active material layer immersed in the electrolyte faces upward. A solid electrolyte layer / negative electrode layer stack is arranged so that the solid electrolyte layer is placed on the positive electrode active material layer, and then the stack is sealed to manufacture an all-solid secondary battery. The positive electrode layer and the negative electrode layer are insulated by an insulating material. A portion of each of the positive electrode collector and the negative electrode collector protrudes out of the sealed battery and is used as a positive electrode layer terminal and a negative electrode layer terminal, respectively.
[0282] Comparative Example 4
[0283] An all-solid secondary battery was prepared according to the same procedure as in Example 8, except that the solid electrolyte of Comparative Example 1 was used instead of the solid electrolyte of Example 1 when preparing the positive electrode layer.
[0284] Evaluation Example 1: X-ray diffraction analysis
[0285] The XRD spectra of the solid electrolytes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were obtained, and representative results thereof are shown in Figure 1 middle.
[0286] XRD spectra were obtained using Cu Kα radiation (1.54056 Angstroms, Å) using X'pert pro (PANalytical).
[0287] like Figure 1 As shown in , the solid electrolyte of Comparative Example 2 has a peak observed in the region of 2θ=12° to 14°, indicating that it has a glass-ceramic crystal structure.
[0288] Meanwhile, in the XRD spectra of the solid electrolytes of Examples 1 to 4, it was found that the peak B intensity (I b ) for the peak A intensity (I a ) peak intensity ratio (I b / I a ) is 3.0 or less. That is, unlike Comparative Example 2, the solid electrolytes of Examples 1 to 4 do not show a diffraction angle pattern that is a characteristic of a crystal and are therefore determined to be a glass phase. In the present disclosure, the intensity of Peak A (I a ) shows the maximum intensity in the region of diffraction angle 2θ = 5° to 9°, and the intensity of peak B (I b ) shows maximum intensity in the region of diffraction angle 2θ = 12° to 14°.
[0289] In addition, XRD analysis of the solid electrolytes of Examples 5 to 7 provided diffraction angle patterns similar to those of the solid electrolyte of Example 1.
[0290] Evaluation Example 2: Measurement of ion conductivity
[0291] The solid electrolyte discs prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were each sputtered with gold (Au) electrodes on both sides thereof, thereby depositing shield electrodes. The impedance of the sample with shield electrodes formed on both sides thereof was measured by a 2-probe method using an impedance analyzer (Solartron 1400A / 1455A impedance analyzer). The frequency range was 1 Hz to 1 megahertz (MHz), and the amplitude voltage was 10 millivolts (mV). The measurement was carried out at 25°C under a dry air atmosphere. The resistance value was obtained by the arc of the Nyquist diagram for the impedance measurement results, and after correcting the electrode area and disc thickness therefor, the ionic conductivity was calculated and shown in Table 3 below.
[0292] As shown in Table 3 below, the solid electrolytes of Examples 1 to 3 and 5 were found to have improved ion conductivity at 60° C. compared to the oxides of Comparative Examples 1 to 3.
[0293] As shown in Table 3 below, the glass oxide of Example 1 was found to have an ion conductivity more than twice that of the undoped glass oxide of Comparative Example 1.
[0294] In Example 2, the oxide Li 0.625 B 0.321 Si 0.044 Cr 0.010 O 0.897 The oxidation state of chromium was determined by XPS spectrum, and the oxidation state of chromium was +3 and +6. 6+The corresponding peak appears at a binding energy of 580.60 electron volts (eV) and is similar to Cr 3+ The corresponding peaks appear at binding energies of 575.20 eV, 576.99 eV, and 578.40 eV.
[0295] In addition, it was found that the crystallization temperature of the oxide of Example 2 was 446°C, and the crystallization temperature of the oxide of Example 5 was 371°C, both of which were greater than the crystallization temperature of Comparative Example 2.
[0296] Evaluation Example 3: Softness Measurement
[0297] The softness of the solid electrolytes prepared in Examples 1 to 5 and Comparative Examples 1 to 3 was evaluated by the following method.
[0298] Softness can be evaluated by the Brinell hardness test method, and the test can measure the Brinell hardness number (BHN) and the softness is defined as 1 / BHN. The test can be performed according to ISO 6506.
[0299] BHN can be expressed as the following Equation 1.
[0300] Equation 1
[0301]
[0302] In Equation 1, P represents the applied load (kilogram force, kgf), D represents the diameter of the indenter ball (mm), and d represents the diameter of the indentation (mm).
[0303] In order to evaluate the softness (deformability) of the sample, the gold contact (Au contact) was first removed by polishing (EIS measurement), and the sample was placed on an alumina plate. On the sample, a stainless steel block with 64 holes was placed with a spacer to prevent the block from contacting the sample, and a zirconia ball was placed on each sample, and different weights were applied by placing a screw with a varying number of nuts on the zirconia ball. During this softness test, the total weight used was 40 grams, which provided sufficient sensitivity. In addition, the test temperature (350°C in this case) was reached at a rate of 5°C / minute and maintained for 3 hours. Then, the diameter of the pit formed at room temperature (25°C) was measured using a microscope.
[0304] Table 3
[0305]
[0306] As shown in Table 3 and Figure 2As shown in , it was found that the solid electrolytes of Examples 1 to 5 had improved softness relative to Comparative Examples 1 to 3, which indicated sufficient interconnection formed based on their soft physical properties. This result shows that the solid electrolytes of Examples 1 to 5 have improved deformability relative to Comparative Examples 1 to 3. In addition, the results of the softness test of the solid electrolytes of Examples 6 to 7 showed a softness of 231 1 / BHN or more, similar to the solid electrolyte of Example 1.
[0307] like Figure 2 As shown in , the solid electrolyte of Comparative Example 2 provides superior softness compared to the solid electrolytes of Comparative Examples 1 and 3, but provides less softness than Examples 1 to 4, and less ion conductivity than Examples 1 to 4.
[0308] Evaluation Example 4: Room temperature charge-discharge test
[0309] The charge-discharge characteristics of the all-solid secondary batteries prepared in Example 8 and Comparative Example 4 were evaluated by the following charge-discharge test conditions. The charge-discharge test was performed while the all-solid secondary batteries were kept in a constant temperature bath at 25°C.
[0310] In the first cycle, the cell was charged at 0.6 mA / cm 2 ) until the battery voltage reaches 4.3 volts (V). Subsequently, the battery is charged at 0.6 mA / cm 2 The battery is discharged at a constant current until the battery voltage reaches 2.8 V.
[0311] From the 2nd cycle to the 13th cycle, the battery was charged at 1.5 mA / cm 2 The battery was then charged at a constant current of 1.5 mA / cm 2 The battery is discharged at a constant current until the battery voltage reaches 2.8 V.
[0312] From the 14th cycle to the 150th cycle, the battery was operated at 2.55 mA / cm 2 The battery was then charged at a constant current of 2.55 mA / cm 2 The battery is discharged at a constant current until the battery voltage reaches 2.8V.
[0313] The charge-discharge test demonstrated that the all-solid secondary battery of Example 8 was subjected to up to 150 cycles without short circuit even at 2.55 mA / cm 2The all-solid secondary battery of Example 8 also provides stable charging and discharging at a current density of , and has a high charge-discharge efficiency. Compared with the all-solid secondary battery of Comparative Example 4, the all-solid secondary battery of Example 8 also has an improved capacity retention rate.
[0314] According to one aspect of the present disclosure, a solid electrolyte having excellent lithium ion conductivity and improved low-temperature formability can be provided. The solid electrolyte can be used to manufacture a secondary battery with improved cycle performance.
[0315] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for limiting purposes. The description of features or aspects in each embodiment should typically be considered to be applicable to other similar features or aspects in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, it will be understood by those of ordinary skill in the art that various changes in form and detail may be made therein without departing from the spirit and scope as defined by the appended claims.
Claims
1. A solid electrolyte, comprising a metal oxide, which comprises lithium, silicon, and boron and at least one metal selected from iron, chromium, lanthanum, or thallium, and, wherein the solid electrolyte has a glass structure, the glass structure comprising 60 mol% or more of lithium, based on the total 100 mol% of the metal and lithium, silicon, and boron, and wherein the solid electrolyte has a softness of 152 1 / BHN or more, where 1 / BHN is the reciprocal of the Brinell hardness value measured according to ISO 6506.
2. The solid electrolyte according to claim 1, wherein in the X-ray diffraction spectrum of the solid electrolyte, the peak intensity ratio of the peak at a diffraction angle of 13° 2θ ± 1.0° 2θ to the peak intensity at a diffraction angle of 5.0° 2θ to 9.0° 2θ is 3.0 or less.
3. The solid electrolyte according to claim 1, wherein the amount of the metal in the oxide is 4 mol% or less, based on the total 100 mol% of the metal, lithium, silicon, and boron.
4. The solid electrolyte according to claim 1, wherein the amount of boron in the oxide is 20 mol% to 60 mol%, based on the total 100 mol% of the metal, lithium, silicon, and boron.
5. The solid electrolyte according to claim 1, wherein the amount of silicon in the metal oxide is 0.1 mol% to 40 mol%, based on the total 100 mol% of the metal, lithium, silicon, and boron.
6. The solid electrolyte according to claim 1, The solid electrolyte has a -7 Ionic conductivity at 60°C of Siemens / cm or greater.
7. The solid electrolyte according to claim 1, wherein the amount of lithium in the oxide is 60 mol% to 80 mol%, based on the total 100 mol% of the metal, lithium, silicon, and boron.
8. The solid electrolyte according to claim 1, wherein the metal oxide is an oxide represented by Formula 1 Formula 1 Li a B b Si c M d O e wherein in Formula 1, M is at least one metal and is at least one of iron, chromium, lanthanum, or thallium, 0.6 ≤ a ≤ 0.8, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.19, 0.01 ≤ d ≤ 0.04, and 0 < e ≤ 1, wherein the sum of a, b, c, and d is 1.
9. The solid electrolyte according to claim 1, wherein the oxide is at least one of Formulas 2 to 5: Formula 2 Li a B b Si c Feb d O e wherein in Formula 2, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1, where the sum of a, b, c, and d is 1, Formula 3 Li a B b Yes c Cr d About e wherein in Formula 3, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1, where the sum of a, b, c, and d is 1, Formula 4 Li a B b Si c Day d O e wherein in Formula 4, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1, where the sum of a, b, c, and d is 1, or Formula 5 Li a B b Si c Tl d O e In Formula 5, 0.6 ≤ a ≤ 0.73, 0.2 ≤ b ≤ 0.38, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.03, and 0 < e ≤ 1, where the sum of a, b, c, and d is 1.
10. The solid electrolyte according to claim 1, wherein the solid electrolyte has a softness of 152 1 / BHN to 260 1 / BHN, where 1 / BHN is the reciprocal of the Brinell hardness value measured according to ISO 6506.
11. A secondary battery, comprising: a positive electrode; a negative electrode current collector; and an electrolyte disposed between the positive electrode and the negative electrode current collector, wherein at least one of the positive electrode or the electrolyte includes the solid electrolyte according to any one of claims 1-10.
12. The secondary battery according to claim 11, wherein the secondary battery includes a lithium battery, an all-solid-state battery, or a multilayer ceramic battery.
13. The secondary battery according to claim 11, wherein the positive electrode includes the solid electrolyte.
14. The secondary battery according to claim 11, wherein a first negative electrode active material layer is disposed between the negative electrode current collector and the electrolyte.
15. The secondary battery according to claim 11, wherein the positive electrode includes a positive electrode current collector, wherein at least one of the positive electrode current collector or the negative electrode current collector includes a base film and a metal layer disposed on one or both sides of the base film, wherein the base film includes a polymer, and the polymer includes at least one of the following: polyethylene terephthalate, polyethylene, polypropylene, polybutylene terephthalate, or polyimide, and wherein the metal layer includes at least one of the following: indium, copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium, lithium, or an alloy thereof.
16. The secondary battery according to claim 11, wherein the electrolyte includes a solid electrolyte, wherein the solid electrolyte includes at least one of the following: a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, or a gel electrolyte, wherein the gel electrolyte includes a polymer gel electrolyte.
17. A method for preparing a solid electrolyte, the method comprising: mixing a metal precursor containing at least one of iron, chromium, lanthanum, or thallium, a lithium precursor, a silicon precursor, a boron precursor, and a solvent to obtain a mixture; performing a first heat treatment on the mixture to provide a first heat-treated mixture; performing a second heat treatment on the first heat-treated mixture to provide a product; and quenching the product to provide the solid electrolyte according to any one of claims 1-10.
18. The method according to claim 17, wherein the second heat treatment includes heat treatment at a temperature higher than the temperature of the first heat treatment, wherein the first heat treatment includes heat treatment at a temperature of 200°C to 400°C, and the second heat treatment includes heat treatment at a temperature of 700°C to 1,000°C.
19. The method according to claim 17, wherein the metal precursor includes at least one of Fe2O3, Cr2O3, La2O2, or Tl2O3, wherein the lithium precursor comprises at least one of Li2O, Li2CO3, LiCl, LiNO3, or Li(OH), wherein the silicon precursor comprises at least one of tetraethyl orthosilicate or SiO2, and The boron precursor comprises at least one of H3BO3 or B2O3.
20. The method of claim 17, Before the first heat treatment, the method further comprises: The mixture is dried to provide a dried mixture, wherein the drying comprises drying at a temperature of 50°C to 90°C.
Citation Information
Patent Citations
Semiconductor device and method for manufacturing the same
KR1020230134364A
Electronic device for predicting cardial nerve disease and thereof method
KR1020240135506A